Polyamides with pendant pigments and related methods - Patents.com
By functionalizing polyamides with pigment pendants, the challenge of non-uniform coloration in polyamide materials is resolved, ensuring consistent color distribution in 3D printed objects through chemically bonded pigment integration.
Patent Information
- Application Number
- JP2020148177
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2020-09-03
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-09-03
AI Technical Summary
Existing methods for incorporating pigments into polyamide materials, such as nylon, result in non-uniform coloration due to difficulties in uniformly mixing particulate pigments, which is particularly problematic in 3D printing applications requiring homogeneous color distribution.
The development of polyamides with pigment pendants from the polyamide backbone chain, achieved by functionalizing metal oxide particles with compounds like epoxy or carboxylic acid to create surface-treated pigments that are chemically bonded to the polyamide, ensuring uniform dispersion of pigments throughout the material.
This approach ensures that objects manufactured using these polyamides maintain uniform coloration over time, as the pigments are integrated uniformly and cannot migrate within the object, addressing the non-uniformity issues in 3D printing.
Smart Images

Figure 0007616845000003 
Figure 0007616845000001 
Figure 0007616845000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to compositions, methods of synthesis, and applications of polyamides having pigments pendant from the polyamide backbone chain. For example, particles may include polyamides having pigments pendant from the polyamide backbone chain. [Background technology]
[0002] Thermoplastic polymers are often used to make extruded objects such as films, bags, particles, and filaments. One example of a thermoplastic polymer is polyamide. Polyamides, like nylon, are off-white polymers that have the ability to withstand high or low temperatures without compromising physical properties. Thus, objects made of polyamide can be used in demanding applications such as power tools, automotive parts, gears, and appliance parts. In some cases, the application may require polyamide parts to be colored. Because pigments are particulate, they may be difficult to mix uniformly in polyamide, which results in uneven coloring of the resulting parts.
[0003] One application where homogeneous incorporation of pigments is particularly important is the rapidly growing technology field of three-dimensional (3D) printing, also known as additive manufacturing. While 3D printing has traditionally been used for rapid prototyping tasks, the technique is increasingly being adopted for the production of commercial and industrial objects that may have completely different structural and mechanical tolerances than the rapid prototypes.
[0004] 3D printing operates by depositing either (a) droplets or streams of molten or solidifiable material, or (b) powder particulates at precise deposition locations for subsequent solidification into larger objects that may have any number of complex shapes. Such deposition and solidification processes are typically performed under computer control to result in layer-by-layer building of larger objects. In certain examples, the consolidation of powder particulates may occur in a 3D printing system that uses a laser to facilitate selective laser sintering (SLS).
[0005] Powder particles that can be used in 3D printing include thermoplastic polymers, including thermoplastic elastomers, metals, and other solidifiable materials. One example of a thermoplastic polymer is nylon. Nylon is an off-white polymer that has the ability to withstand high or low temperatures without losing its physical properties. Therefore, nylon can be used in demanding applications such as power tools, automotive parts, gears, and appliance parts.
[0006] When using particulate pigments in 3D printing, the particulates should be evenly dispersed throughout the small molten droplets or power particulates, or the coloring of the final object will be uneven. Summary of the Invention
[0007] The present disclosure relates to compositions, methods of synthesis, and applications of polyamides having pigments pendant from the polyamide backbone chain. For example, particles may include polyamides having pigments pendant from the polyamide backbone chain.
[0008] Described herein is a method that includes functionalizing metal oxide particles attached to pigment particles with an epoxy-bearing compound to produce a surface-treated pigment with a pendant epoxy, and reacting the pendant epoxy with a polyamide to obtain a pigment-pendant polyamide (PP-polyamide).
[0009] Described herein is a method that includes functionalizing metal oxide particles attached to pigment particles with silica particles having a carboxylic acid surface treatment to produce a surface treated pigment having pendant carboxylic acids, converting the pendant carboxylic acids to pendant acid chlorides, and reacting the pendant acid chlorides with polyamides to obtain PP-polyamides.
[0010] Described herein are compositions comprising a polyamide having a pigment pendant from the backbone of the polyamide, the pigment comprising metal oxide particles on the surface of the pigment particle.
[0011] Also described herein are articles that include the aforementioned compositions.
[0012] Described herein is a method comprising mixing a mixture comprising a polyamide having a PP-polyamide, a carrier fluid immiscible with the PP-polyamide and optionally an emulsion stabilizer at a temperature above the melting point or softening temperature of the PP-polyamide and at a shear rate high enough to disperse the PP-polyamide in the carrier fluid, and cooling the mixture below the melting point or softening temperature of the PP-polyamide to form solidified particles, the solidified particles comprising the PP-polyamide and, if present, the emulsion stabilizer associated with the outer surface of the solidified particles.
[0013] Described herein are compositions comprising particles comprising PP-polyamide, the particles having a circularity of about 0.90 to about 1.0, the particles optionally further comprising one or more emulsion stabilizers associated with the outer surface of the particles.
[0014] Also disclosed herein is a method comprising depositing the particles (including PP-polyamide), optionally in combination with other thermoplastic polymer particles, onto a surface in a particular shape, and once deposited, heating at least a portion of the particles to promote consolidation of the particles to form a consolidated body. [Brief description of the drawings]
[0015] The following figures are included to illustrate certain aspects of the present disclosure and should not be viewed as exclusive configurations. The disclosed subject matter is capable of considerable modification, permutations, combinations, and equivalents in form and function, as will occur to those of ordinary skill in the art having the benefit of this disclosure.
[0016] [Figure 1] FIG. 1 is a flow diagram of a non-limiting exemplary method 100 of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present disclosure relates to compositions, methods of synthesis, and methods of application of polyamides with pigments pendant from the backbone chain of the polyamide, also referred to herein as polyamides with pendant pigments or PP-polyamides. The polyamides are functionalized with pigment particles so that objects incorporating the PP-polyamides have more uniformly dispersed pigments.
[0018] The present disclosure also relates to particles comprising polyamides having pigments pendant from the polyamide backbone (also referred to herein as pigment-pendant polyamides or PP-polyamides) and related methods. More specifically, the present disclosure includes methods for making highly spherical polymer particles comprising one or more PP-polyamides and optionally one or more other thermoplastic polymers. The polymer particles may be useful, inter alia, as starting materials for additive manufacturing.
[0019] The polymer particles described herein can be produced, for example, by a melt-emulsion method in which one or more PP-polyamides and, optionally, one or more additional thermoplastic polymers, if used, are dispersed as a melt in a carrier fluid that is immiscible with the PP-polyamides and additional thermoplastic polymers. A sufficient amount of shear force is applied to the mixture to cause the polymer melt to form droplets in the carrier fluid.
[0020] Because the pigments are pendant from the polyamide backbone chain, objects produced by additive manufacturing methods containing these particles should maintain a uniform color over time because the pigments cannot move within the object.
[0021] Definitions and Test Methods As used herein, the term "pigment" refers to a particle that absorbs and / or refracts ultraviolet or visible light. As used herein, "surface treated pigment" refers to a pigment having oxide particles chemically and / or physically bonded to the surface of the pigment particle.
[0022] As used herein, the term "immiscible" refers to a mixture of components that, when combined, form two or more phases that have a melting point of less than 5% by weight with each other at room temperature at ambient pressure, or at the melting point of the components if solid at room temperature. For example, polyethylene oxide with a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65°C. Thus, if a material is liquid at room temperature and the polyethylene oxide has a melting point of less than 5% by weight at 65°C, the polyethylene oxide is immiscible with the material.
[0023] As used herein, the term "thermoplastic polymer" refers to a plastic polymeric material that reversibly softens and hardens on heating and cooling. Thermoplastic polymers include thermoplastic elastomers.
[0024] As used herein, the term "elastomer" refers to a copolymer that includes a crystalline "hard" segment and an amorphous "soft" segment. In the case of polyurethanes, the crystalline segment may include the portion of the polyurethane that includes urethane functionality and optional chain extenders, and the soft segment may include, for example, a polyol.
[0025] As used herein, the term "polyurethane" refers to the polymeric reaction product between a diisocyanate, a polyol, and an optional chain extender.
[0026] As used herein, the term "oxide" refers to both metal and non-metal oxides. For purposes of this disclosure, silicon is considered to be a metal.
[0027] As used herein, the terms "associated," "association," and grammatical variations thereof between an emulsion stabilizer and a surface refer to chemical bonding and / or physical adhesion of the emulsion stabilizer to the surface. Without being limited by theory, it is believed that the association described herein between the polymer and the emulsion stabilizer is primarily a physical adhesion by hydrogen bonding and / or other mechanisms. However, some chemical bonding may occur.
[0028] As used herein, the term "embedded" with respect to nanoparticles and the surface of a polymer particle refers to the nanoparticles extending at least partially into the surface such that the polymer is in contact with the nanoparticles to a greater extent than would occur if the nanoparticles were simply deposited on the surface of the polymer particle.
[0029] In this specification, D10, D50, D90 and diameter span are mainly used in this specification to describe particle size.As used in this specification, the term "D10" refers to the diameter at which 10% of the sample (by volume unless otherwise specified) is made up of particles with a diameter less than the diameter value.As used in this specification, the term "D50" refers to the diameter at which 50% of the sample (by volume unless otherwise specified) is made up of particles with a diameter less than the diameter value.As used in this specification, the term "D90" refers to the diameter at which 90% of the sample (by volume unless otherwise specified) is made up of particles with a diameter less than the diameter value.
[0030] As used herein, the terms "diameter span" and "span" and "span size" when referring to diameter provide a measure of the spread of the particle size distribution and are calculated as (D90-D10) / D50 (again, each D value is based on volume unless otherwise noted).
[0031] Particle size may be determined by light scattering techniques using a Malvern MASTERSIZER™ 3000 or analysis of optical digital micrographs. Unless otherwise stated, light scattering techniques are used to analyze particle size.
[0032] For light scattering techniques, the control sample was glass beads with diameters in the range of 15 μm to 150 μm, trade name Quatily Audit Standards QAS4002, obtained from Malvern Analytical Ltd. Samples were analyzed as dry powders unless otherwise stated. Analyzed particles were dispersed in air and analyzed using the AERO S dry powder dispersion module with the MASTERSIZER™ 3000. Particle size was derived using the instrument software from a plot of volume density as a function of size.
[0033] Particle size measurements and diameter spans can also be determined by optical digital microscopy. Optical images are obtained using a Keyence VHX-2000 digital microscope using version 2.3.5.1 software (system version 1.93) for particle size analysis.
[0034] As used herein, when referring to sieves, the hole / screen size is as set forth in the USA Standard Sieve (ASTM E11-17).
[0035] As used herein, the terms "circularity" and "sphericity" for particles refer to how close a particle is to a perfect sphere. To determine circularity, an optical microscope image of the particle is taken. The perimeter (P) and area (A) of the particle in the plane of the microscope image are calculated (e.g., using a SYSMEX FPIA 3000 Particle Shape and Size Analyzer available from Malvern Instruments). The circularity of a particle is expressed as C EA / P and C EA is the circumference of a circle whose area corresponds to the area of the actual particle (A).
[0036] As used herein, the term "sintering window" refers to the difference between the melting temperature (Tm) onset and the crystallization temperature (Tc) onset, i.e., (Tm-Tc) onset. Tm, Tm(onset), Tc, and Tc(onset) are measured by differential scanning calorimetry according to ASTM E794-06(2018) using a heating rate of 10°C / min and a cooling rate of 10°C / min.
[0037] As used herein, the term "shear force" refers to stirring or similar processes that induce mechanical agitation in a fluid.
[0038] As used herein, the term "aspect ratio" refers to the ratio of length divided by width, where the length is greater than the width.
[0039] Unless otherwise stated, the melting points of polymers are determined according to ASTM E794-06(2018) using a heating and cooling rate of 10° C. / min.
[0040] Unless otherwise stated, the softening temperature or softening point of a polymer is determined by ASTM D6090-17. The softening temperature may be measured by using a cup and ball apparatus available from Mettler-Toledo using a 0.50 gram sample at a heating rate of 1° C. / min.
[0041] Angle of repose is a measure of the flowability of a powder. Angle of repose measurements were determined using a Hosokawa Micron Powder Characteristics Tester PT-R using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices."
[0042] Hausner ratio (H r ) is a measure of the powder's flowability, and H r =ρ tap / ρ bulk ρ is calculated by bulkis the bulk density according to ASTM D6393-14, and ρ tap is the tap density according to ASTM D6393-14.
[0043] As used herein, the viscosity of a dispersion fluid is the kinematic viscosity at 25° C., as measured by ASTM D445-19, unless otherwise specified. For commercially obtained dispersion fluids (e.g., PDMS oil), the kinematic viscosity data cited herein is that provided by the manufacturer, whether measured according to the aforementioned ASTM or another standard measurement technique.
[0044] Pigment-Pendant Polyamide In general, the compositions, synthesis methods, and application methods of the present disclosure use a linker that chemically bonds the oxide particles of the surface-treated pigment to the nitrogens of the polyamide. The result is a PP-polyamide. Because the surface-treated pigment has some oxide particles on the surface, the surface-treated pigment particles can act as a crosslinker for the polyamide.
[0045] Examples of polyamides include, but are not limited to, polycaproamide (nylon 6, polyamide 6, or PA6), poly(hexamethylene succinamide) (nylon 4,6, polyamide 4,6, or PA4,6), polyhexamethylene adipamide (nylon 6,6, polyamide 6,6, or PA6,6), polypentamethylene adipamide (nylon 5,6, polyamide 5,6, or PA5,6), polyhexamethylene sebacinamide (nylon 6,10, polyamide 6,10, or PA6,10), polyundecaneamide (nylon 11, polyamide 11, or PA11), polydodecanamide (nylon 12, polyamide 12, or PA12), polyhexamethylene terephthalamide, Polyamides include nylon 6T, polyamide 6T, or PA6T, nylon 10,10 (polyamide 10,10 or PA10,10), nylon 10,12 (polyamide 10,12 or PA10,12), nylon 10,14 (polyamide 10,14 or PA10,14), nylon 10,18 (polyamide 10,18 or PA10,18), nylon 6,18 (polyamide 6,18 or PA6,18), nylon 6,12 (polyamide 6,12 or PA6,12), nylon 6,14 (polyamide 6,14 or PA6,14), nylon 12,12 (polyamide 12,12 or PA12,12), semi-aromatic polyamides, aromatic polyamides (aramids), and the like, and any combination thereof. Copolyamides may also be used. Examples of copolyamides include, but are not limited to, PA11 / 10,10, PA6 / 11, PA6,6 / 6, PA11 / 12, PA10,10 / 10,12, PA10,10 / 10,14, PA11 / 10,36, PA11 / 6,36, PA10,10 / 10,36, PA6T / 6,6, etc., and any combination thereof. Examples of polyamide elastomers include, but are not limited to, polyesteramides, polyetheresteramides, polycarbonate-esteramides, and polyether-block-amide elastomers. In this specification, a polyamide followed by a single number is a polyamide having that number of backbone carbons between each nitrogen.A polyamide having a first number followed by a comma and a second number is a polyamide having the first number of backbone carbons between the nitrogens of segments that do not have a pendant =O and the second number of backbone carbons between the nitrogens of segments that have a pendant =O. As a non-limiting example, nylon 6,10 is [NH-(CH2)6-NH-CO-(CH2)8-CO]. n A polyamide followed by a number(s) backslash number(s) is a copolymer of the polyamide designated by the numbers before and after the backslash.
[0046] Pigments may impart color, metallic color, and / or pearlescent color to the polyamide, such as gold pigments, silver aluminum pigments, bronze pigments, gold bronze pigments, stainless steel pigments, zinc pigments, iron pigments, tin pigments, and copper pigments. Examples of pigments include, but are not limited to, synthetic mica (e.g., fluorophlogopite), natural mica (e.g., muscovite), talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, acicular pigments (e.g., BiOCl, colored glass fibers, α-Fe2O3, and α-FeOOH), CaSO4, iron oxide, chromium oxide, carbon black, metallic effect pigments (e.g., Al flakes and bronze), optically variable pigments (OVPs), liquid crystal polymer pigments (LCPs), holographic pigments, and the like, and any combination thereof.
[0047] Examples of metal oxides that may be coatings on the surface of the pigment include, but are not limited to, titanium dioxide, titanium suboxide, titanium oxynitride, Al2O3, Fe2O3, Fe3O4, SnO2, Cr2O3, ZnO, CuO, NiO, zirconium oxide, titanium iron oxide (iron titanate), other metal oxides, and the like, and any combination thereof. Preferred metal oxides include TiO2 and / or Fe2O3.
[0048] The surface-treated pigment may be any combination of the above pigments with one or more metal oxides, alone or in a mixture in a uniform or continuous layer. For example, the surface-treated pearlescent pigment may be a pigment based on a platelet-shaped, transparent or translucent substrate, such as layered silicate, coated with colored or colorless metal oxides, such as titanium oxide and iron oxide, alone or in a mixture in a uniform or continuous layer. Particularly preferred surface-treated pigments include TiO2-coated mica, Fe2O3-coated mica, TiO2 / Fe2O3-coated mica, and any combination thereof.
[0049] Examples of commercially available surface treated pigments include, but are not limited to, REFLEX™ pigments (synthetic mica-based pearlescent pigments available from CQV), IRIODIN™ (mica-based metal oxide coated pearlescent pigments available from Merck) (e.g., IRIODIN™ 300 “Gold Pearl” and IRIODIN™ 100 “Silver Pearl”), SUNGEM™ (glass platelet based pigments available from Sun Chemical), SUNMICA (mica-based pigments available from Sun Chemical), SYNCRYSTAL™ (metal oxide coated synthetic fluorophlogopite flakes available from Eckart), and the like, as well as any combination thereof. Other metallic pearlescent pigments from Merck include TIMIRON® Bronze MP60 with a D50 volume average particle size (50% of the pigments have a volume size less than the stated size) of 22-37 micrometers, TIMIRON® Copper MP-65 with a D50 size of 22-37 micrometers, COLORONA® Oriental Beige with a D50 size of 3-10 micrometers, COLORONA® Aborigine Amber with a D50 size of 18-25 micrometers, COLORONA® Passion Orange with a D50 size of 18-25 micrometers, COLORONA® Bronze Fine with a D50 size of 7-14, COLORONA® Bronze with a D50 size of 18-25 micrometers, and COLORONA® Bronze with a D50 size of 28-42 micrometers. COLORONA® Copper Sparkle, COLORONA® Copper Fine with D50 size of 7-14 micrometers, COLORONA® Copper with D50 size of 18-25 micrometers, COLORONA® Copper Sparkle with D50 size of 25-39 micrometers, COLORONA® Red with D50 size of 18-25 micrometersBrown, COLORONA® Russet with a D50 size of 18 to 25 micrometers, COLORONA® Tibetan Ochre with a D50 size of 18 to 25 micrometers, COLORONA® Sienna Fine with a D50 size of 7 to 14 micrometers, COLORONA® Sienna with a D50 size of 18 to 25 micrometers, COLORONA® Bordeaux with a D50 size of 18 to 25 micrometers, COLORONA® Glitter Bordeaux, and COLORONA® Chameleon with a D50 size of 18 to 25 micrometers. Also suitable are Merck mica-based pigments having a metal oxide particle coating, such as Merck silver white pigments, including TIMIRON® Super Silk MP-1005 with a D50 size of 3 to 10 micrometers, TIMIRON® Super Sheen MP-1001 with a D50 size of 7 to 14 micrometers, TIMIRON® Super Silver Fine with a D50 size of 9 to 13 micrometers, TIMIRON® Pearl Sheen MP-30 with a D50 size of 15 to 21 micrometers, TIMIRON® Satin MP-11171 with a D50 size of 11 to 20 micrometers, TIMIRON® Ultra Luster MP-111 with a D50 size of 18 to 25 micrometers, TIMIRON® Star Luster MP-111 with a D50 size of 18 to 25 micrometers, and TIMIRON® Pearl Flake with a D50 size of 22 to 37 micrometers. MP-10, TIMIRON® Super Silver with D50 size of 17-26 micrometers, TIMIRON® Sparkle with D50 size of 28-38 micrometers MP-47, TIMIRON® Arctic with D50 size of 19-25 micrometersSilver, XIRONA® Silver having a D50 size of 15 to 22 micrometers, RONASTAR® Silver having a D50 size of 25 to 45 micrometers, and any combination thereof. For very bright colours, examples from Merck include COLORONA® Carmine Red with a D50 size of 10-60 micrometers to give a red sheen effect, COLORONA® Magenta with a D50 size of 18-25 micrometers to give a pink-violet sheen effect, COLORONA® Light Blue with a D50 size of 18-25 micrometers to give a light blue sheen effect, COLORONA® Dark Blue with a D50 size of 18-25 micrometers to give a dark blue sheen effect, COLORONA® Majestic Green with a D5 of 18-25 micrometers to give a green sheen colour, COLORONA® Brilliant Green with a D5 of 19-26 micrometers to give a greenish gold sheen colour, COLORONA® Egyptian Emerald with a D50 of 18-25 micrometers to give a dark green sheen effect, COLORONA® Patagonian with a D50 of 18-25 micrometers to give a purple sheen effect. Purple, etc., and any combination thereof. DORADO®PX 4001, DORADO®PX 4261, DORADO®PX 4271, DORADO®PX 4310, DORADO®PX 4331, DORADO®PX 4542, PHOENIX®XT, PHOENIX®XT 2001, PHOENIX®XT 3001, PHOENIX®XT 4001, PHOENIX®XT 5001, PHOENIX®PX 1000, PHOENIX®PX 1001, PHOENIX®PX 1221, PHOENIX®PX 1231, PHOENIX®PX 1241, PHOENIX®PX 1251, PHOENIX®PX1261, PHOENIX®PX 1271, PHOENIX®PX 1310, PHOENIX®PX 1320, PHOENIX®PX 1502, PHOENIX®PX 1522, PHOENIX®PX 1542, PHOENIX®PX 2000, PHOENIX®PX 2000 L, PHOENIX®PX 2001, PHOENIX®PX 2011, PHOENIX®PX 2021, PHOENIX®PX 2221, PHOENIX®PX 2231, PHOENIX®PX 2241, PHOENIX®PX 2251, PHOENIX®PX 2261, PHOENIX®PX 2271, PHOENIX® PX 3001, PHOENIX® PX 4000, PHOENIX® PX 4001, PHOENIX® PX 4221, PHOENIX® PX 4231, PHOENIX® PX 4241, PHOENIX® PX 4251, PHOENIX® PX 4261, PHOENIX® PX 4271, PHOENIX® PX 4310, PHOENIX® PX 4320, PHOENIX® PX 4502, PHOENIX® PX 4522, PHOENIX® PX 4542, PHOENIX® PX 5000, PHOENIX® PX 5001, PHOENIX® PX 5310, PHOENIX®PXMica-based special effect pigments having a D50 of about 18 micrometers to about 50 micrometers manufactured by Eckart, such as 5331, and the like, as well as any combinations thereof, may also be used. DF-1667 16 micron, DF-2750 55 micron, DF-3500 27 micron, DF-3622 35 micron, DF-554 15 micron, DF-L-520AR 20 micron, LED-1708AR 20 micron, LED-2314AR 13 micron, SILBERCOTE™ PC 0452Z 55 micron, SILBERCOTE™ PC 1291X 47 micron, SILBERCOTE™ 36 micron, SILBERCOTE™ PC 3331X 36 micron, SILBERCOTE™ PC 4352Z 31 micron, SILBERCOTE™ PC 4852X 33 micron, SILBERCOTE™ PC 20 micron Special effect pigments such as Silberline aluminum flake pigments, such as 6222X, 27 micrometer SILBERCOTE™ PC 6352Z, 25 micrometer SILBERCOTE™ PC 6802X, 14 micrometer SILBERCOTE™ PC 8152Z, 14 micrometer SILBERCOTE™ PC 8153X, 16 micrometer SILBERCOTE™ PC 8602X, 20 micrometer SILVET® / SILVEX® 890 series, 16 micrometer SILVET® / SILVEX® 950 series, and the like, and any combination thereof, may be used.
[0050] The surface treated pigment may have an average diameter (or D50) of about 1 micrometer to about 500 micrometers (or about 1 micrometer to about 25 micrometers, or about 5 micrometers to about 50 micrometers, or about 25 micrometers to about 200 micrometers, or about 100 micrometers to about 300 micrometers, or about 250 micrometers to about 500 micrometers). Without wishing to be bound by theory, it is believed that larger pigment particles impart more colorant, metallic, and / or pearlescent effects to the polyamide.
[0051] Scheme 1 below is a first non-limiting exemplary synthesis of PP-polyamide. More specifically, the bifunctional coupling reagent contains, for example, alkoxysilane terminal groups and glycidyl functional groups. The alkoxysilane groups (illustrated as Si(-OCH3)3 groups, one or more of such groups may be hydrolyzed to -OH groups) are attached to the surface of oxide particles (MOx particles) on the surface of the pigment. Although the silane is shown to be attached only to the metal oxide particles, the silane may also be attached to the surface of the pigment depending on the composition of the pigment. The epoxy of the glycidyl moiety then reacts with the nitrogen of the amide in the polyamide (illustrated using nylon 6) to obtain the PP-polyamide. Although the epoxy is shown as a terminal epoxy, the bifunctional coupling reagent may have one or more glycidyl functional groups (or epoxy groups) including terminal, pendant, or both terminal and pendant such groups. As shown, the pigment is chemically linked to four polyamide chains, and also shows that the pigment may be a crosslinker.
[0052] [ka]
[0053] Examples of silanes having a glycidyl moiety include, but are not limited to, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane, and 1,3-bis(3- G glycidoxypropyl)tetramethylsiloxane, 2-(3,4 epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 5,6-epoxyhexyltriethoxysilane, and the like, and any combination thereof.
[0054] Silane coupling reaction can be carried out by known methods, such as those outlined in the article entitled Glycidyl Alkoxysilanc Reactivities Towards Simple Nucleophiles in Organic Media for Improved Molecular Structure Definition in Hybrid Materials by X. Guillory et al., Royal Society of Chemistry Advances 2016, 6, 74087-74099. The outcome of the reaction depends heavily on the reaction conditions, whether the solvent is aqueous, organic or ionic liquid medium, the temperature concentration, the catalyst, and the choice of acidic or basic conditions. Also, from the cited US Patent No. 7,998,649, a metal oxide coated mica pigment, which is a silica or titania particle surface, is reacted with (3-glycidoxypropyl)trimethoxysilane or (3-glycidoxypropyl)triethoxysilane or diethoxy(3-glycidoxypropyl)methylsilane or 1,3-bis(3-glycidyloxypropyl)tetramethylsiloxane in a molar ratio of 0.85 to 0.15 with an appropriate amount of ethanol or methanol, water, and ammonia to prepare an epoxide-containing composition. The solution is then stirred at room temperature or slightly elevated to 40° C. for about 2 to about 10 hours.
[0055] In another example, the silane coupling reaction can be carried out by hydrolytic deposition of silanes (B. Arkles, CHEMTECH, 7, 766, 1977), where silane oligomers are hydrogen bonded with OH groups of the substrate. During drying or curing, covalent bonds with the substrate are formed while losing water. Methods for increasing reactivity include transesterification catalysts and transesterification agents that increase the acidity of hydroxyl groups on the substrate by hydrogen bonding. Transesterification catalysts include tin compounds such as dibutyldiacetoxytin, and titanates such as titanium isopropoxide. Incorporation of a transesterification catalyst of about 2% to about 3% by weight of the silane often effectively promotes the reaction and deposition, in other cases it includes tetrabutyl titanate, or the reaction can be promoted by adding a catalytic amount of an amine such as benzyldimethylamine. The reaction conditions may include that the coupling agent may be present at about 0.1% to about 5% by weight relative to the pigment, the reaction time may be about 4 hours to about 12 hours, the temperature may be about 50°C to about 120°C, an ethanol solvent is preferred over methanol, and the water in the solvent is at a concentration of about 1% to about 5% by weight to promote hydrolysis of the silane during deposition onto the surface.
[0056] In yet another embodiment, the silane coupling reaction can be carried out by anhydrous liquid deposition, where a toluene, tetrahydrofuran, and / or hydrocarbon solution is prepared containing about 1% to about 10% by weight of the silane. The mixture is refluxed with the substrate to be treated (pigment in this example) for about 12 hours to about 24 hours. The treated pigment is washed with a solvent. The solvent is then removed by air drying or explosion-proof oven drying. No further curing is required.
[0057] The reaction of the epoxide groups on the metal pigment with the polyamide may be carried out under an atmosphere (nitrogen or argon) at a temperature of about 70°C to about 200°C (or about 70°C to about 150°C, or about 125°C to about 200°C) in the presence of an organic solvent such as tetrahydrofuran, dimethylformamide or toluene. The mixture is then stirred at elevated temperature for about 24 hours. After the mixture is cooled to room temperature, the grafted polymer is filtered and washed to remove organic impurities and unreacted starting reagents.
[0058] Scheme 2 below is a second non-limiting exemplary synthesis of PP-polyamide. More specifically, silica particles with surface functionality with at least one carboxylic acid (which may be terminal, pendant, or both terminal and pendant as shown) are grafted onto metal oxide particles (although they may also be grafted to the pigment depending on the pigment composition). The carboxylic acid from the functionalized silica particles is then converted to an acid chloride, which reacts with the nitrogen of the amide in the polyamide (shown using nylon 6) to obtain the PP-polyamide. As shown, the pigment is chemically bonded to four polyamide chains, which indicates that the surface coating pigment (the surface of the pigment and / or the surface of the metal oxide particle) may also be a crosslinker.
[0059] [ka]
[0060] Examples of functionalized silica particles include, but are not limited to, 3-aminopropyl-(3-oxobutanoic) acid functionalized silica, 3-propylsulfonic acid functionalized silica gel, propylcarboxylic acid functionalized silica gel, triaminetetraacetic acid functionalized silica gel, propionyl chloride functionalized silica gel, 3-carboxypropyl functionalized silica gel, aminomethylphosphonic acid (AMPA) functionalized silica gel, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) functionalized silica gel, and the like, and any combination thereof.
[0061] The grafting reaction of functionalized silica to pigment can be carried out by known methods. Similar to the glycidyl-functionalized coated pigment of scheme 1, the silane containing reactive alkoxy (OR) functional group can react with the surface hydroxyl group of metal oxide particles and / or pigment. When the silane solution is applied onto the surface hydroxyl group of metal oxide particles and / or pigment, the free silanol group first forms a hydrogen bond with the hydroxyl (-OH) group on the metal oxide particles and / or pigment at ambient temperature. Then, the SiO2 bond is formed by condensation between the silanol group and the -OH group on the surface of the SiO2 bond.
[0062] The conversion of carboxylic acid to more reactive acid chloride can be carried out by known methods. For example, oxalic acid chloride (COCl)2 and / or thionyl chloride SOCl2 may be used as chlorinating agent together with a catalyst. Solvents for the reaction may include, but are not limited to, dimethylformamide, dichloromethane, and the like, and any combination thereof.
[0063] The acid chloride / polyamide reaction with the polyamide may be carried out by known methods. For example, the pigment having acid chloride functionality may be melt mixed with the polyamide at about 125° C. to about 250° C. (or about 125° C. to about 200° C., or about 150° C. to about 225° C., or about 200° C. to about 250° C.) for about 15 minutes to about 1 hour or more (or about 15 minutes to about 30 minutes, or about 20 minutes to about 40 minutes, or about 30 minutes to about 1 hour).
[0064] Schemes 1 and 2 provide non-limiting examples of synthetic routes for producing surface-treated pigments with pendant epoxy or carboxylic acid moieties. Other reaction schemes will be apparent to those skilled in the art.
[0065] The surface treated pigments having pendant epoxy or carboxylic acid moieties are reacted with a polyamide to provide the PP-polyamides described herein.
[0066] Via Scheme 1, Scheme 2, or another coupling reaction scheme, the PP-polyamides described herein may have a weight ratio of pigment to polyamide of from about 1:10 to about 1:1000 (or from about 1:10 to about 1:200, or from about 1:100 to about 1:500, or from about 1:250 to about 1:1000).
[0067] PP-Polyamide Applications The PP-polyamides described herein may be used to manufacture various objects (or articles). The PP-polyamides described herein may be used alone or in combination with other thermoplastic polymers (e.g. polyamides that do not contain light absorbers and / or other thermoplastic polymers).Examples of thermoplastic polymers that may be used in conjunction with one or more PP-polyamides of the present disclosure include, but are not limited to, polyamides (e.g., polyamides not bound to pigments), polyurethanes, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfides, polysulfones, polyetherketones, polyamideimides, polyetherimides, polyetheresters, polyether blocks, and polyamide blocks. copolymers including ethylene / vinyl monomers (PEBA or polyether block amides), grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and the like, and any combination thereof. Copolymers comprising one or more of the foregoing may also be used in the methods and systems described herein.
[0068] If necessary, a compatibilizer may be used when combining the PP-polyamides described herein with other thermoplastic polymers. The compatibilizer can improve the blending efficiency and / or effectiveness of the polymers. Examples of polymeric compatibilizers include, but are not limited to, PROPOLDER™ MPP2020 20 (polypropylene, available from Polygroup Inc.), PROPOLDER™ MPP2040 40 (polypropylene, available from Polygroup Inc.), NOVACOM™ HFS2100 (maleic anhydride functionalized high density polyethylene polymer, available from Polygroup Inc.), KEN-REACT™ CAPS™ L™ 12 / L (organometallic coupling agent, available from Kenrich Petrochemicals), KEN-REACT™ CAPOW™ L™ 12 / H (organometallic coupling agent, available from Kenrich Petrochemicals), KEN-REACT™ LICA™ 12 (organometallic coupling agent, available from Kenrich Petrochemicals), KEN-REACT™ CAPS™ KPR™ 12 / LV (organometallic coupling agent, available from Kenrich Petrochemicals), and KEN-REACT™ CAPS™ KPR™ 12 / LV (organometallic coupling agent, available from Kenrich Petrochemicals). Petrochemicals), KEN-REACT™ CAPOW™ KPR™ 12 / H (an organometallic coupling agent, available from Kenrich Petrochemicals), KEN-REACT™ Titanate & Zirconate (an organometallic coupling agent, available from Kenrich Petrochemicals),Petrochemicals), VISTAMAXX™ (ethylene-propylene copolymer, available from ExxonMobil), SANTOPRENE™ (thermoplastic vulcanizate of ethylene-propylene-diene rubber and polypropylene, available from ExxonMobil), VISTALON™ (ethylene-propylene-diene rubber, available from ExxonMobil), EXACT™ (plastomers, available from ExxonMobil) EXXEL OR™ (polymer resin, available from ExxonMobil), FUSABOND™ M603 (random ethylene copolymer, available from Dow), FUSABOND™ E226 (anhydride modified polyethylene, available from Dow), BYNEL™ 41E710 (coextrudable adhesive resin, available from Dow), SURLYN™ 1650 (ionomer resin, available from Dow), FUSABOND™ P353 (chemically modified polypropylene copolymer, available from Dow), available from Dow), ELVALOY™ PTW (ethylene terpolymer, available from Dow), ELVALOY™ 3427AC (copolymer of ethylene and butyl acrylate, available from Dow), LOTADER™ AX8840 (ethylene acrylate-based terpolymer, available from Arkema), LOTADER™ 3210 (ethylene acrylate-based terpolymer, available from Arkema), LOTADER™ 3410 (ethylene acrylate-based terpolymer, available from Arkema), mer, available from Arkema), LOTADER™ 3430 (ethylene acrylate based terpolymer, available from Arkema), LOTADER™ 4700 (ethylene acrylate based terpolymer, available from Arkema), LOTADER™ AX8900 (ethylene acrylate based terpolymer, available from Arkema), LOTADER™ 4720 (ethylene acrylate based terpolymer, available from Arkema), BAXXODUR™ EC 301 (amine for epoxy, available from BASF), BAXXODUR™ EC 311 (amine for epoxy, available from BASF), BAXXODUR™ EC303 (amine for epoxies, available from BASF), BAXXODUR™ EC 280 (amine for epoxies, available from BASF), BAXXODUR™ EC 201 (amine for epoxies, available from BASF), BAXXODUR™ EC 130 (amine for epoxies, available from BASF), BAXXODUR™ EC 130 (amine for epoxies, available from BASF), BAXXODUR™ EC 110 (amine for epoxies, available from BASF), styrenic, polypropylene, polyamide, polycarbonate, EASTMAN™ G-3003 (maleic anhydride grafted polypropylene, available from Eastman), RETAIN™ (polymer modifier, available from Dow), AMPLIFY TY™ (maleic anhydride grafted polymer, available from Dow), INTUNE™ (olefin block copolymer, available from Dow), and the like, and any combination thereof.
[0069] Methods for manufacturing the objects include, but are not limited to, melt extrusion, injection molding, compression molding, melt spinning, melt emulsification, spray drying (e.g., forming particles), cryogenic milling (or cryogenic grinding), freeze-drying polymer dispersions, precipitation of polymer dispersions, and the like, and any hybrids thereof.
[0070] Examples of articles that may be produced by such methods, where PP-polyamide may be all or part of the article, include, but are not limited to, particles, films, packaging, toys, household goods, automotive parts, aerospace / aircraft related parts, containers (e.g., for food, beverage, cosmetic, personal care compositions, pharmaceutical applications, etc.), shoe soles, furniture parts, home decor, plastic gears, screws, nuts, bolts, cable ties, jewelry, artwork, sculptures, medical articles, prostheses, orthopedic implants, fabrications to aid learning in education, 3D anatomical models to aid in surgery, robots, biomedical devices (orthotics), home appliances, dental tools, electronic equipment, sporting goods, etc. Additionally, the particles may be useful in applications including, but not limited to, paints, powder coatings, inkjet materials, electrophotographic toners, 3D printing, etc.
[0071] Additionally, the PP-Polyamide described herein may have a specific chemical fingerprint that is useful for identifying an object, tracking an object, authenticating an object, and / or determining the health of an object. Furthermore, the configuration where the PP-Polyamide is located within the object is another layer to obtain the fingerprint of the object to identify the object, track the object, authenticate the object, and / or determine the health of the object.
[0072] Methods for identifying, tracking, authenticating and / or determining the health of an object may include (a) exposing an object comprising PP-polyamide to electromagnetic radiation, (b) sensing one or more spectra associated with the absorbed and / or re-emitted electromagnetic radiation, and (c) comparing the spectrum to known spectra of light absorbers used on the object or a portion of the object. Optionally, the location of the spectral region on the object may be compared to known locations where the spectral region should be. The comparison(s) may be used to identify and / or authenticate the object. For tracking, the comparison(s) may be made and / or the detected spectrum and / or spectral region may be recorded in a database together with the physical location of the object. Furthermore, the health of an object that wears and / or cracks may be confirmed. For example, a core portion of the article may include a light absorber, and an outer portion may cover the core portion and may not include a light absorber (or may include a different light absorber). When the spectra are then compared, the appearance of the spectral signature of a light absorber in the core may indicate that the object is at or near the end of its life.
[0073] As a non-limiting example, a 3D printing process of the present disclosure includes depositing particles comprising one or more PP-polyamides of the present disclosure (and optionally one or more other thermoplastic polymers and / or one or more compatibilizers) onto a surface in a particular shape, and once deposited, heating at least a portion of the particles to promote consolidation of the particles to form a consolidated body (object), the consolidated body having a porosity of about 1% or less after consolidation. For example, the heating and consolidation of the thermoplastic polymer particles may be performed in a laser-based 3D printing device, such that the heating and consolidation is performed by selective laser sintering.
[0074] As a non-limiting example, a 3D printing process of the present disclosure may include extruding a filament comprising one or more PP-polyamides of the present disclosure (and optionally one or more other thermoplastic polymers and / or one or more compatibilizers) through an orifice, where the filament becomes a polymer melt upon extrusion; depositing the polymer melt as a first layer on a platform; cooling the layer; depositing an additional layer of the polymer melt on the first layer; cooling the additional layer; and repeating the deposition and cooling of at least one additional layer to generate a 3D shape.
[0075] Yet another non-limiting example may include extruding a polymer melt comprising one or more PP-polyamides of the present disclosure (and optionally one or more other thermoplastic polymers and / or one or more compatibilizers) through an orifice to produce films, fibers (or filaments), particles, pellets, and the like.
[0076] Thermoplastic polymer particles and method of manufacture The figure is a flow diagram of a non-limiting exemplary method 100 of the present disclosure. Thermoplastic polymer 102 (including one or more PP-polyamides and optionally one or more other thermoplastic polymers), carrier fluid 104, and optionally emulsion stabilizer 106 are combined (108) to produce mixture 110. Components 102, 104, and 106 may be added in any order and may include mixing and / or heating during the process 108 of combining components 102, 104, and 106.
[0077] The mixture 110 is then processed 112 by applying a sufficiently high shear force to the mixture 110 at a temperature above the melting or softening temperature of the thermoplastic polymer 102 to form a melt emulsion 114. Because the temperature is higher than the melting or softening temperature of the thermoplastic polymer 102, the thermoplastic polymer 102 becomes a polymer melt. The shear rate should be sufficient to disperse the polymer melt as droplets (i.e., polymer emulsion 114) in the dispersion medium 104. Without being bound by theory, it is believed that, all other factors being equal, increasing the shear force should decrease the size of the polymer melt droplets in the dispersion medium 104. However, at some point, there may be diminishing returns from increasing the shear force and decreasing the droplet size, or there may be a breakup into droplet contents that reduces the quality of the particles produced.
[0078] The molten emulsion 114 inside and / or outside the mixing vessel is then cooled (116) to solidify the polymer droplets into thermoplastic polymer particles (also referred to as solidified thermoplastic polymer particles). The cooled mixture 118 is then processed (120) to isolate the thermoplastic polymer particles 122 from other components 124 (e.g., the carrier fluid 104, excess emulsion stabilizer 106, etc.) and the thermoplastic polymer particles 122 may be washed or otherwise purified. The thermoplastic polymer particles 122 include the thermoplastic polymer 102 and, if present, at least a portion of the emulsion stabilizer 106 that coats the outer surface of the thermoplastic polymer particles 122. The emulsion stabilizer 106, or a portion thereof, may be deposited as a uniform coating on the thermoplastic polymer particles 122. In some cases, depending on non-limiting factors such as temperature (including cooling rate), type of thermoplastic polymer 102, and type and size of emulsion stabilizer 106, the nanoparticles of emulsion stabilizer 106 may become at least partially embedded within the outer surface of the thermoplastic polymer particles 122 in the course of associating with the thermoplastic polymer particles 122. Even if the embodiment is not practiced, at least the nanoparticles within the emulsion stabilizer 106 may remain tightly associated with the thermoplastic polymer particles 122, facilitating their further use. In contrast, dry blending of already formed thermoplastic polymer particulates (e.g., formed by cryogenic grinding or precipitation processes) with a flow aid such as silica nanoparticles does not result in a robust, uniform coating of the flow aid on the thermoplastic polymer particulates.
[0079] Advantageously, the carrier fluids and wash solvents of the systems and methods described herein (e.g., method 100) can be regenerated and reused. Those skilled in the art will recognize any necessary washing of spent carrier fluids and solvents that may be required for the regeneration process.
[0080] The thermoplastic polymer 102 and the dispersion medium 104 should be selected such that the thermoplastic polymer 102 and the dispersion medium 104 are immiscible at various processing temperatures (e.g., from room temperature to the process temperature). An additional factor that may be considered is the difference (e.g., difference or ratio) in viscosity between the molten polyamide 102 and the dispersion medium 104 at the process temperature. The difference in viscosity may affect the droplet breakup and particle size distribution. Without being bound by theory, it is believed that if the viscosities of the molten polyamide 102 and the dispersion medium 104 are too similar, the circularity of the overall product may be reduced, and the particles may become more ovoid and more elongated structures are observed.
[0081] Thermoplastic polymer 102 includes one or more PP-polyamides and optionally one or more other thermoplastic polymers. Examples of other thermoplastic polymers include, but are not limited to, polyamides, polyurethanes, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfides, polysulfones, polyetherketones, polyamideimides, polyetherimides, polyetheresters, copolymers including polyether blocks and polyamide blocks (PEBA or polyether block a). amides), grafted or ungrafted thermoplastic polyolefins, functionalized or unfunctionalized ethylene / vinyl monomer polymers, functionalized or unfunctionalized ethylene / alkyl (meth)acrylates, functionalized or unfunctionalized (meth)acrylic acid polymers, functionalized or unfunctionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and the like, and any combination thereof. Copolymers comprising one or more of the foregoing may also be used in the methods and systems of the present disclosure.
[0082] The other thermoplastic polymers in the compositions and methods of the present disclosure may be elastomeric or non-elastomeric. Some of the above examples of other thermoplastic polymers may be elastomeric or non-elastomeric depending on the exact composition of the polymer. For example, polyethylene, which is a copolymer of ethylene and propylene, may be elastomeric or non-elastomeric depending on the amount of propylene in the polymer.
[0083] Thermoplastic elastomers generally fall within one of six classes: styrenic block copolymers, thermoplastic polyolefin elastomers, thermoplastic vulcanizates (also called elastomeric alloys), thermoplastic polyurethanes, thermoplastic copolyesters, and thermoplastic polyamides (typically block copolymers containing polyamides). Examples of thermoplastic elastomers can be found in Handbook of Thermoplastic Elastomers, 2nd ed., BMW Alker and CP Rader, eds., Van Nostrand Reinhold, New York, 1988. Examples of thermoplastic elastomers include, but are not limited to, elastomeric polyamides, polyurethanes, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, polybutadiene, polyisoprene, styrenic block copolymers, and polyacrylonitrile), silicones, and the like. The elastomeric styrenic block copolymer may include at least one block selected from the group consisting of isoprene, isobutylene, butylene, ethylene / butylene, ethylene-propylene, and ethylene-ethylene / propylene. More specific examples of elastomeric styrenic block copolymers include, but are not limited to, poly(styrene-ethylene / butylene), poly(styrene-ethylene / butylene-styrene), poly(styrene-ethylene / propylene), styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene-ethylene-propylene), poly(styrene-butadiene-styrene), poly(styrene-butylene-butadiene-styrene), and the like, and any combination thereof.
[0084] Examples of polyamides include, but are not limited to, the polyamides described above. Examples of polyamide elastomers include, but are not limited to, polyesteramides, polyetheresteramides, polycarbonate-esteramides, and polyether-block-amide elastomers.
[0085] Examples of polyurethanes include, but are not limited to, polyether polyurethanes, polyester polyurethanes, mixed polyether and polyester polyurethanes, and the like, and any combination thereof. Examples of thermoplastic polyurethanes include, but are not limited to, poly[4,4'-methylenebis(phenylisocyanate)-alt-1,4-butanediol / di(propylene glycol) / polycaprolactone], ELASTOLLAN® 1190A (polyether polyurethane elastomer, available from BASF), ELASTOLLAN® 1190A10 (polyether polyurethane elastomer, available from BASF), and the like, and any combination thereof.
[0086] Compatibilizers may optionally be used to improve the efficiency and effectiveness of blending PP-polyamide with one or more thermoplastic polymers. Examples of polymeric compatibilizers include, but are not limited to, those listed above.
[0087] Thermoplastic polymer 102 (including one or more PP-polyamides and optionally one or more other thermoplastic polymers) may have a melting point or softening temperature of about 50° C. to about 450° C. (or about 50° C. to about 125° C., or about 100° C. to about 175° C., or about 150° C. to about 280° C., or about 200° C. to about 350° C., or about 300° C. to about 450° C.).
[0088] Thermoplastic polymer 102 may have a glass transition temperature (ASTM E1356-08(2014) using 10°C / min heating and cooling rates) of about -50°C to about 400°C (or about -50°C to about 0°C, or about -25°C to about 50°C, or about 0°C to about 150°C, or about 100°C to about 250°C, or about 150°C to about 300°C, or about 200°C to about 400°C).
[0089] The thermoplastic polymer 102 may optionally include an additive. Typically, the additive is present prior to adding the thermoplastic polymer 102 to the mixture 110. Thus, in the thermoplastic polymer melt droplets and the resulting thermoplastic polymer particles, the additive is dispersed throughout the thermoplastic polymer. Accordingly, for clarity, this additive is referred to herein as an "internal additive." The internal additive may be blended with the thermoplastic polymer immediately prior to pre-forming the mixture 110 or well.
[0090] When describing amounts of ingredients in compositions described herein (e.g., mixture 110 and thermoplastic polymer particles 122), the amounts are weight percent based on the thermoplastic polymer 102 without the internal additive. For example, a composition that includes 1% emulsion stabilizer by weight of 100 g of thermoplastic polymer 102 that includes 10% internal additive and 90% thermoplastic polymer by weight is a composition that includes 0.9 g of emulsion stabilizer, 90 g of thermoplastic polymer, and 10 g of internal additive.
[0091] The internal additive may be present in the thermoplastic polymer 102 at about 0.1% to about 60% by weight (or about 0.1% to about 5%, or about 1% to about 10%, or about 5% to about 20%, or about 10% to about 30%, or about 25% to about 50%, or about 40% to about 60% by weight) of the thermoplastic polymer 102. For example, the thermoplastic polymer 102 may include about 70% to about 85% by weight of the thermoplastic polymer and about 15% to about 30% by weight of the internal additive, such as glass fiber or carbon fiber.
[0092] Examples of internal additives include, but are not limited to, fillers, reinforcing agents, pigments, pH adjusters, and the like, and combinations thereof. Examples of fillers include, but are not limited to, glass fibers, glass particles, mineral fibers, carbon fibers, oxide particles (e.g., titanium dioxide and zirconium dioxide), metal particles (e.g., aluminum powder), and the like, and any combinations thereof. Examples of pigments include, but are not limited to, organic pigments, inorganic pigments, carbon black, and the like, and any combinations thereof.
[0093] The thermoplastic polymer 102 may be present in the mixture 110 at about 5% to about 60% by weight (or about 5% to about 25% by weight, or about 10% to about 30% by weight, or about 20% to about 45% by weight, or about 25% to about 50% by weight, or about 40% to about 60% by weight) of the combined thermoplastic polymer 102 and dispersion medium 104.
[0094] A suitable dispersion medium 104 has a viscosity at 25° C. of about 1,000 cSt to about 150,000 cSt (or about 1,000 cSt to about 60,000 cSt, or about 40,000 cSt to about 100,000 cSt, or about 75,000 cSt to about 150,000 cSt).
[0095] Examples of the dispersion medium 104 include, but are not limited to, silicone oils, fluorinated silicone oils, perfluorinated silicone oils, polyethylene glycols, alkyl terminated polyethylene glycols (e.g., C1-C4 terminal alkyl groups such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty esters, higher fatty acids, fatty alcohols, fatty acid modified polysiloxanes, fatty alcohol modified polysiloxanes, polyoxyalkylene modified polysiloxanes, and the like, and any combination thereof. Examples of silicone oils include, but are not limited to, polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and the like, and any combination thereof. The dispersion medium 104 may have one or more phases. For example, a fatty acid-modified polysiloxane and an aliphatic alcohol-modified polysiloxane (preferably with similar chain lengths as the fatty acid and the aliphatic alcohol) may form a single-phase dispersion medium 104. In another example, a dispersion medium 104 including a silicone oil and an alkyl-terminated polyethylene glycol may form a two-phase dispersion medium 104.
[0096] The dispersion medium 104 may be present in the mixture 110 at about 40% to about 95% by weight (or about 75% to about 95% by weight, or about 70% to about 90% by weight, or about 55% to about 80% by weight, or about 50% to about 75% by weight, or about 40% to about 60% by weight) of the combined thermoplastic polymer 102 and dispersion medium 104.
[0097] In some cases, the dispersion medium 104 has a density of about 0.6 g / cm 3 ~Approx. 1.5g / cm 3 and the thermoplastic polymer 102 may have a density of about 0.7 g / cm 3 ~Approx. 1.7g / cm 3 and the thermoplastic polymer has a density similar to, lower than, or higher than the density of the dispersion medium.
[0098] Emulsion stabilizers used in the methods and compositions of the present disclosure may include nanoparticles (e.g., oxide nanoparticles, carbon black, polymeric nanoparticles, and combinations thereof), surfactants, and the like, and any combinations thereof.
[0099] The oxide nanoparticles may be metal oxide nanoparticles, non-metal oxide nanoparticles, or mixtures thereof. Examples of oxide nanoparticles include, but are not limited to, silica, titania, zirconia, alumina, iron oxide, copper oxide, tin oxide, boron oxide, cerium oxide, thallium oxide, tungsten oxide, and the like, and any combination thereof. Mixed metal oxides and / or non-metal oxides, such as aluminosilicates, borosilicates, and aluminoborosilicates, are also included in the term metal oxide. The oxide nanoparticles may be hydrophilic or hydrophobic and may be natural particles or the result of surface treatment of the particles. For example, silica nanoparticles with hydrophobic surface treatments, such as dimethylsilyl, trimethylsilyl, and the like, may be used in the methods and compositions of the present disclosure. In addition, silicas with functional surface treatments, such as methacrylate functional groups, may be used in the methods and compositions of the present disclosure. Non-functionalized oxide nanoparticles may be suitable for use as well.
[0100] Commercially available examples of silica nanoparticles include, but are not limited to, AEROSIL® available from Evonik (e.g., AEROSIL® R812S (with hydrophobically modified surface and 260±30 m 2 / g BET surface area), AEROSIL® RX50 (hydrophobically modified surface and 35±10m 2 / g BET surface area), AEROSIL® 380 (hydrophobically modified surface and 380±30m 2 / g) silica nanoparticles), and any combination thereof.
[0101] Carbon black is another type of nanoparticle that may be present as an emulsion stabilizer in the compositions and methods disclosed herein. Various grades of carbon black are familiar to those skilled in the art, any of which may be used herein. Other nanoparticles capable of absorbing infrared radiation may be used as well.
[0102] Polymer nanoparticles are another type of nanoparticle that may be present as an emulsion stabilizer in the present disclosure.Suitable polymer nanoparticles may include one or more polymers that are thermosetting and / or crosslinked so that they do not melt when processed by melt emulsification according to the present disclosure.High molecular weight thermoplastic polymers with high melting or decomposition points may also comprise suitable polymer nanoparticle emulsion stabilizers.
[0103] The nanoparticles can have an average diameter (D50 based on volume) of about 1 nm to about 500 nm (or about 10 nm to about 150 nm, or about 25 nm to about 100 nm, or about 100 nm to about 250 nm, or about 250 nm to about 500 nm).
[0104] Nanoparticles are about 10m 2 / g~about 500m 2 / g (or about 10m 2 / g~about 150m 2 / g, or about 25m 2 / g~about 100m 2 / g, or about 100m 2 / g ~ approx. 250m 2 / g, or 250m 2 / g~about 500m 2 / g).
[0105] The nanoparticles may be included in the mixture 110 at a concentration of about 0.01% to about 10% by weight (or about 0.01% to about 1% by weight, or about 0.1% to about 3% by weight, or about 1% to about 5% by weight, or about 5% to about 10% by weight), based on the weight of the thermoplastic polymer 102.
[0106] The surfactant may be anionic, cationic, nonionic, or zwitterionic. Examples of surfactants include, but are not limited to, sodium dodecyl sulfate, sorbitan oleate, poly[dimethylsiloxane-co-[[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane], docusate sodium (sodium 1,4-bis(2-ethylhexoxy)-1,4-dioxobutane-2-sulfonate), and the like, and any combination thereof. Commercially available examples of surfactants include, but are not limited to, CALFAX® DB-45 (sodium dodecyl diphenyl oxide disulfonate, available from Pilot Chemicals), SPAN® 80 (sorbitan maleate nonionic surfactant), MERPOL® surfactants (available from Stepan Company), TERGITOL™ TMN-6 (water soluble nonionic surfactant, available from DOW), TRITON® X-100 (octylphenol ethoxylate, available from SigmaAldrich), IGEPAL® CA-520 (polyoxyethylene (5) isooctylphenyl ether, available from SigmaAldrich), BRIJ® S10 (polyethylene glycol octadecyl ether, available from SigmaAldrich), and the like, and any combination thereof.
[0107] The surfactant may be included in mixture 110 at a concentration of about 0.01% to about 10% by weight (or about 0.01% to about 1% by weight, or about 0.5% to about 2% by weight, or about 1% to about 3% by weight, or about 2% to about 5% by weight, or about 5% to about 10% by weight), based on the weight of polyamide 102. Alternatively, mixture 110 may be free of (or absent from) a surfactant.
[0108] The weight ratio of nanoparticles to surfactant may be from about 1:10 to about 10:1 (or from about 1:10 to about 1:1, or from about 1:5 to about 5:1, or from about 1:1 to about 10:1).
[0109] As mentioned above, the components 102, 104, and 106 may be added in any order and may include mixing and / or heating during the process 108 including the components 102, 104, and 106. For example, the emulsion stabilizer 106 may first be dispersed in the carrier fluid 104 prior to adding the thermoplastic polymer 102, optionally with heating of the dispersion. In another non-limiting example, the thermoplastic polymer 102 may be heated to produce a polymer melt to which the carrier fluid 104 and the emulsion stabilizer 106 are added together or in any order. In yet another non-limiting example, the thermoplastic polymer 102 and the carrier fluid 104 may be mixed at a temperature above the melting point or softening temperature of the thermoplastic polymer 102 and at a shear rate sufficient to disperse the thermoplastic polymer melt in the carrier fluid 104. The emulsion stabilizer 106 may then be added to form the mixture 110 and maintained at suitable process conditions for a set period of time.
[0110] Combining 108 the components 102, 104, and 106 in any combination may occur in a mixing device and / or another suitable vessel used for process 112. As a non-limiting example, the thermoplastic polymer 102 may be heated to a temperature above the melting point or softening temperature of the thermoplastic polymer 102 in the mixing device used for process 112, and the emulsion stabilizer 106 may be dispersed in the dispersion medium 104 in a separate vessel. The dispersion may then be added to a melt of the thermoplastic polymer 102 in the mixing device used for process 112.
[0111] The mixing equipment used in process 112 to produce the molten emulsion 114 should be capable of maintaining the molten emulsion 114 at a temperature above the melting point or softening temperature of the thermoplastic polymer 102 and applying a shear rate sufficient to disperse the polymer melt as droplets in the dispersion medium 104.
[0112] Examples of mixing equipment used in process 112 to produce molten emulsion 114 include, but are not limited to, extruders (e.g., continuous extruders, batch extruders, etc.), stirred reactors, blenders, reactors with in-line homogenizer systems, etc., and equipment derived therefrom.
[0113] Processing 112 at suitable process conditions (eg, temperature, shear rate, etc.) for a set period of time and forming a molten emulsion 114.
[0114] The temperature of process 112 and formation of molten emulsion 114 should be a temperature above the melting point or softening temperature of thermoplastic polymer 102 and below the decomposition temperature of any of components 102, 104, and 106 in mixture 110. For example, the temperature of process 112 and formation of molten emulsion 114 may be about 1° C. to about 50° C. (or about 1° C. to about 25° C., or about 5° C. to about 30° C., or about 20° C. to about 50° C.) above the melting point or softening temperature of thermoplastic polymer 102, provided that the temperature of process 112 and formation of molten emulsion 114 is below the decomposition temperature of any of components 102, 104, and 106 in mixture 110.
[0115] The shear rate of process 112 and formation of melt emulsion 114 should be high enough to disperse the polymer melt as droplets in dispersion medium 104. The droplets should include droplets having a diameter of about 1000 μm or less (or from about 1 μm to about 1000 μm, or from about 1 μm to about 50 μm, or from about 10 μm to about 100 μm, or from about 10 μm to about 250 μm, or from about 50 μm to about 500 μm, or from about 250 μm to about 750 μm, or from about 500 μm to about 1000 μm).
[0116] The time for maintaining the temperature and shear rate for process 112 and forming molten emulsion 114 may be from 10 seconds to 18 hours or more (or from 10 seconds to 30 minutes, or from 5 minutes to 1 hour, or from 15 minutes to 2 hours, or from 1 hour to 6 hours, or from 3 hours to 18 hours). Without being bound by theory, it is believed that a steady state in droplet size is reached at which point process 112 may be stopped. That time may depend on, among other things, the temperature, the shear rate, the composition of the thermoplastic polymer 102, the composition of the dispersion medium 104, and the composition of the emulsion stabilizer 106.
[0117] The molten emulsion 114 may then be cooled (116). The cooling 116 may be slow (e.g., allowing the molten emulsion to cool under ambient conditions) to fast (e.g., rapid cooling). For example, the cooling rate may range from about 10° C. / hour to about 100° C. / second to nearly instantaneous with rapid cooling (e.g., dry ice) (or from about 10° C. / hour to about 60° C. / hour, or from about 0.5° C. / minute to about 20° C. / minute, or from about 1° C. / minute to about 5° C. / minute, or from about 10° C. / minute to about 60° C. / minute, or from about 0.5° C. / second to about 10° C. / second, or from about 10° C. / second to about 100° C. / second).
[0118] During cooling, little or no shear force may be applied to the molten emulsion 114. In some cases, the shear force applied during heating may be applied during cooling.
[0119] The cooled mixture 118 resulting from cooling 116 of the molten emulsion 114 contains solidified thermoplastic polymer particles 122 (or simply thermoplastic polymer particles) and other components 124 (e.g., the dispersion medium 104, excess emulsion stabilizer 106, etc.). The thermoplastic polymer particles may be dispersed in the dispersion medium or may settle in the dispersion medium.
[0120] The cooled mixture 118 may then be processed (120) into separate thermoplastic polymer particles 122 (or simply thermoplastic polymer particles 122) from other components 124. Suitable processing includes, but is not limited to, washing, filtering, centrifuging, decanting, the like, and any combination thereof.
[0121] The solvent used to wash the thermoplastic polymer particles 122 should generally be (a) miscible with the carrier fluid 104 and (b) non-reactive (e.g., non-swelling and non-melting) with the thermoplastic polymer 102. The choice of solvent will depend, among other things, on the composition of the carrier fluid and the composition of the thermoplastic polymer 102.
[0122] Examples of solvents include, but are not limited to, hydrocarbon solvents (e.g., pentane, hexane, heptane, octane, cyclohexane, cyclopentane, decane, dodecane, tridecane, and tetradecane), aromatic hydrocarbon solvents (e.g., benzene, toluene, xylene, 2-methylnaphthalene, and cresol), ether solvents (e.g., diethyl ether, tetrahydrofuran, diisopropyl ether, and dioxane), ketone solvents (e.g., acetone and methyl ethyl ketone), alcohol solvents (e.g., methanol, ethanol, isopropanol, and n-propanol), ester solvents (e.g., ethyl acetate, methyl acetate, butyl acetate, butyl propionate, and butyl butyrate), halogenated solvents (e.g., chloroform, bromoform, 1,2-dichloromethane, 1,2-dichloroethane, carbon tetrachloride, chlorobenzene, and hexafluoroisopropanol), water, and the like, and any combination thereof.
[0123] The solvent may be removed from the thermoplastic polymer particles 122 by drying using a suitable method such as air drying, heat drying, vacuum drying, freeze drying, or a hybrid thereof. Heating may be preferably performed at a temperature below the glass transition point of the thermoplastic polymer (e.g., about 50° C. to about 150° C.).
[0124] The thermoplastic polymer particles 122 after separation from other components 124 may, if desired, be further classified to produce purified thermoplastic polymer particles 128. For example, to narrow the particle size distribution (or reduce the diameter span), the thermoplastic polymer particles 122 may be passed through a sieve having a pore size of about 10 μm to about 250 μm (or about 10 μm to about 100 μm, or about 50 μm to about 200 μm, or about 150 μm to about 250 μm).
[0125] In another exemplary purification technique, the thermoplastic polymer particles 122 may be washed with water to remove the surfactant while retaining substantially all of the nanoparticles associated with the surface of the thermoplastic polymer particles 122. In yet another exemplary purification technique, the thermoplastic polymer particles 122 may be blended with additives to obtain a desired end product. For clarity, such additives are referred to herein as "external additives" because they are blended with the thermoplastic particles 122 or other particles resulting from the methods described herein after the particles have solidified. Examples of external additives include flow aids, other polymer particles, fillers, and the like, and any combination thereof.
[0126] In some cases, the surfactant used in the production of the thermoplastic polymer particles 122 may be unnecessary in downstream applications. Accordingly, yet another exemplary purification technique may include at least substantially removing the surfactant from the thermoplastic polymer particles 122 (e.g., by washing and / or pyrolysis).
[0127] The thermoplastic polymer particles 122 and / or the refined thermoplastic polymer particles 128 (referred to as particles 122 / 128) may be characterized by composition, physical structure, and the like.
[0128] As mentioned above, the emulsion stabilizer is at the interface between the polymer melt and the dispersion medium. As a result, when the mixture cools, the emulsion stabilizer remains at or near that interface. Thus, the structure of the particles 122 / 128 generally includes the emulsion stabilizer (a) dispersed on the outer surface of the particles 122 / 128 and / or (b) embedded in the outer portion (e.g., the outer 1% by volume) of the particles 122 / 128.
[0129] Additionally, if voids are formed within the polymer melt droplets, the emulsion stabilizer 106 should generally be present (and / or embedded) at the interface between the interior of the void and the thermoplastic polymer. The voids generally do not contain thermoplastic polymer. Rather, the voids may contain, for example, a dispersion medium, air, or may be empty. The particles 122 / 128 may contain about 5% or less (or about 0.001% to about 5% by weight, or about 0.001% to about 0.1% by weight, or about 0.01% to about 0.5% by weight, or about 0.1% to about 2% by weight, or about 1% to about 5% by weight) of the dispersion medium by weight of the particles 122 / 128.
[0130] The thermoplastic polymer 102 may be present in the particles 122 / 128 at about 90% to about 99.5% by weight (or about 90% to about 95% by weight, or about 92% to about 97% by weight, or about 95% to about 99.5% by weight) of the particles 122 / 128.
[0131] If included, emulsion stabilizer 106 may be present in particle 122 / 128 at about 10% or less by weight of particle 122 / 128 (or from about 0.01% to about 10% by weight, or from about 0.01% to about 1% by weight, or from about 0.5% to about 5% by weight, or from about 3% to about 7% by weight, or from about 5% to about 10% by weight). When purified to at least substantially remove surfactant or another emulsion stabilizer, emulsion stabilizer 106 may be present in particle 128 at less than 0.01% by weight (or from 0% to about 0.01% by weight, or from 0% to 0.001% by weight).
[0132] In forming the thermoplastic microparticles according to the disclosure herein, at least a portion of the nanoparticles, such as silica nanoparticles, may be disposed as a coating on the outer surface of the thermoplastic microparticle. At least a portion of the surfactant, if used, may be associated with the outer surface as well. The coating may be substantially uniformly disposed on the outer surface. As used herein with respect to the coating, the term "substantially uniform" refers to a uniform coating thickness at the surface locations covered by the coating composition (e.g., nanoparticles and / or surfactant), particularly the entire outer surface. The emulsion stabilizer 106 may form a coating that covers at least 5% (or from about 5% to about 100%, or from about 5% to about 25%, or from about 20% to about 50%, or from about 40% to about 70%, or from about 50% to about 80%, or from about 60% to about 90%, or from about 70% to about 100%) of the surface area of the particle 122 / 128. When purified to at least substantially remove surfactant or another emulsion stabilizer, emulsion stabilizer 106 may be present in particle 128 on less than 25% (or from 0% to about 25%, or from about 0.1% to about 5%, or from about 0.1% to about 1%, or from about 1% to about 5%, or from about 1% to about 10%, or from about 5% to about 15%, or from about 10% to about 25%) of the surface area of particle 128. The coverage of emulsion stabilizer 106 on the outer surfaces of particles 122 / 128 may be determined using image analysis of scanning electron microscope images (SEM micrographs). The emulsion stabilizer 106 may form a coating that covers at least 5% (or from about 5% to about 100%, or from about 5% to about 25%, or from about 20% to about 50%, or from about 40% to about 70%, or from about 50% to about 80%, or from about 60% to about 90%, or from about 70% to about 100%) of the surface area of the particle 122 / 128. When purified to at least substantially remove surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particle 128 on less than 25% (or from 0% to about 25%, or from about 0.1% to about 5%, or from about 0.1% to about 1%, or from about 1% to about 5%, or from about 1% to about 10%, or from about 5% to about 15%, or from about 10% to about 25%) of the surface area of the particle 128. The coverage of emulsion stabilizer 106 on the outer surface of particles 122 / 128 may be determined using image analysis of SEM micrographs.
[0133] The particles 122 / 128 may have a D10 of about 0.1 μm to about 125 μm (or about 0.1 μm to about 5 μm, about 1 μm to about 10 μm, about 5 μm to about 30 μm, or about 1 μm to about 25 μm, or about 25 μm to about 75 μm, or about 50 μm to about 85 μm, or about 75 μm to about 125 μm), a D50 of about 0.5 μm to about 200 μm (or about 0.5 μm to about 10 μm, or about 5 μm to about 50 μm, or about 30 μm to about 100 μm, or about 30 μm to about 70 μm, or about 25 μm to about 50 μm, or about 50 μm to about 100 μm, or about 75 μm to about 150 μm, or about 100 μm to about 200 μm), and a D90 of about 3 μm to about 300 μm (or about 3 μm to about 15 μm, or about 10 μm to about 50 μm, or about 25 μm to about 75 μm, or about 70 μm to about 200 μm, or about 60 μm to about 150 μm, or about 150 μm to about 300 μm), with D10 < D50 < D90. The particles 122 / 128 may also have a diameter span of about 0.2 to about 10 (or about 0.2 to about 0.5, or about 0.4 to about 0.8, or about 0.5 to about 1.0, or about 1 to about 3, or about 2 to about 5, or about 5 to about 10). Without limitation, a diameter span value of 1.0 or more is considered wide, and a diameter span value of 0.75 or less is considered narrow. Without limitation, a diameter span value of 1.0 or more is considered wide, and a diameter span value of 0.75 or less is considered narrow.
[0134] In a first non-limiting example, the particles 122 / 128 may have a D10 of about 0.1 μm to about 10 μm, a D50 of about 0.5 μm to about 25 μm, and a D90 of about 3 μm to about 50 μm, with D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 0.2 to about 2.
[0135] In a second non-limiting example, the particles 122 / 128 may have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, with D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 1.0 to about 2.5.
[0136] In a third non-limiting example, the particles 122 / 128 can have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, with D10 < D50 < D90. The particles 122 / 128 can have a diameter span of about 0.6 to about 1.5.
[0137] In a fourth non-limiting example, the particles 122 / 128 can have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, with D10 < D50 < D90. The particles 122 / 128 can have a diameter span of about 0.2 to about 1.2.
[0138] In a fifth non-limiting example, the particles 122 / 128 can have a D10 of about 1 μm to about 50 μm (or about 5 μm to about 30 μm, or about 1 μm to about 25 μm, or about 25 μm to about 50 μm), a D50 of about 25 μm to about 100 μm (or about 30 μm to about 100 μm, or about 30 μm to about 70 μm, or about 25 μm to about 50 μm, or about 50 μm to about 100 μm), and a D90 of about 60 μm to about 300 μm (or about 70 μm to about 200 μm, or about 60 μm to about 150 μm, or about 150 μm to about 300 μm), with D10 < D50 < D90. The particles 122 / 128 can also have a diameter span of about 0.4 to about 3 (or about 0.6 to about 2, or about 0.4 to about 1.5, or about 1 to about 3).
[0139] The particles 122 / 128 may have a circularity of about 0.9 or more (or about 0.90 to about 1.0, or about 0.93 to about 0.99, or about 0.95 to about 0.99, or about 0.97 to about 0.99, or about 0.98 to 1.0).
[0140] The particles 122 / 128 may have an angle of repose of about 25° to about 45° (or about 25° to about 35°, or about 30° to about 40°, or about 35° to about 45°).
[0141] Particles 122 / 128 can have a Hausner ratio of about 1.0 to about 1.5 (or about 1.0 to about 1.2, or about 1.1 to about 1.3, or about 1.2 to about 1.35, or about 1.3 to about 1.5).
[0142] Particle 122 / 128 is approximately 0.3 g / cm 3 ~about 0.8g / cm 3 (or about 0.3 g / cm 3 ~about 0.6g / cm 3 , or about 0.4 g / cm 3 ~about 0.7g / cm 3 , or about 0.5 g / cm 3 ~about 0.6g / cm 3 , or about 0.5 g / cm 3 ~about 0.8g / cm 3 ) bulk density.
[0143] Depending on the temperature and shear rate of the process 112, and the composition and relative concentrations of the components 102, 104, and 106, different shapes of the structures that make up the particles 122 / 128 have been observed. Typically, the particles 122 / 128 include substantially spherical particles (having a circularity of about 0.97 or greater). However, other structures have been observed in the particles 122 / 128, including disk structures and elongated structures. Thus, the particles 122 / 128 may include one or more of: (a) substantially spherical particles having a circularity of 0.97 or greater; (b) disk structures having an aspect ratio of about 2 to about 10; and (c) elongated structures having an aspect ratio of 10 or greater. Each of the (a), (b), and (c) structures has an emulsion stabilizer dispersed on the outer surfaces of the (a), (b), and (c) structures, and / or an emulsion stabilizer embedded in the outer portions of the (a), (b), and (c) structures. At least some of the (a), (b), and (c) structures may be aggregated, for example, the elongated structures of (c) may be located on the surface of a substantially spherical particle of (a).
[0144] Particles 122 / 128 may have a sintering time within 10° C., preferably within 5° C., of the sintering time of thermoplastic polymer 102 (which includes one or more PP-polyamides and optionally one or more other thermoplastic polymers).
[0145] 3D printing The particles comprising PP-polyamides described herein may be useful in a variety of applications, including 3D printing. The 3D printing process of the present disclosure may include depositing the PP-polyamide particles of the present disclosure (e.g., particles comprising one or more PP-polyamides and optionally one or more other thermoplastic polymers) on a surface in a specific shape, and heating at least a portion of the particles once deposited to promote consolidation of the particles and form a consolidated body (object), the consolidated body having a porosity of about 1% or less after consolidation. For example, the heating and consolidation of the thermoplastic polymer particles may be performed in a laser-based 3D printing device, such that the heating and consolidation is performed by selective laser sintering.
[0146] Examples of objects that can be 3D printed using the thermoplastic polymer particles of the present disclosure include, but are not limited to, containers (e.g., for use in food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, toys, furniture parts and home decor items, plastic gears, screws, nuts, bolts, cable ties, automotive parts, medical articles, prostheses, orthopedic implants, aerospace / aviation related parts, the creation of artificial objects to aid in education and learning, 3D anatomical models to aid in surgery, robots, biomedical devices (prosthetics), home appliances, dental tools, electronic devices, sporting goods, and the like.
[0147] Other applications of particles comprising one or more PP-polyamides of the present disclosure include, but are not limited to, use as fillers in paints and powder coatings, inkjet materials and electrophotographic toners, and the like.
[0148] Exemplary embodiments A first non-limiting exemplary embodiment is a method that includes functionalizing metal oxide particles attached to pigment particles with a compound having an epoxy (including terminal, pendant, or both terminal and pendant such groups) to produce a surface-treated pigment having a pendant epoxy, and reacting the pendant epoxy with a polyamide to obtain a pigment-pendant polyamide (PP-polyamide).A first non-limiting exemplary embodiment is element 1, in which the compound having an epoxide is (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane, and 1,3-bis(3-dodisilyloxypropyl)tetramethylsiloxane, 2-(3,4 epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 5,6-ethylenedioxypropylmethyldimethoxy ... Element 1; and Element 2; wherein the metal oxide particles include one or more selected from the group consisting of titanium dioxide, titanium suboxide, titanium oxynitride, Al2O3, Fe2O3, Fe3O4, SnO2, Cr2O3, ZnO, CuO, NiO, zirconium oxide, and titanium iron oxide; and Element 3; wherein the pigment particles include synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, and any combination thereof. Element 3, comprising one or more selected from the group consisting of iron oxide, needle pigment, CaSO4, iron oxide, chromium oxide, carbon black, metal effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments; and element 4, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecanamide, polyhexamethylene terephthalamide, nylon 10,10 , nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamide, aromatic polyamide, copolymers of any of these, and any combinations thereof; element 5, wherein the reaction of the pendant epoxy with the polyamide is conducted at from about 70° C. to about 200° C.; and element 6, wherein the weight ratio of pigment to polyamide is from about 1:10 to about 1:1000.Examples of combinations include, but are not limited to, element 1 combined with one or more of elements 2-6, element 2 combined with one or more of elements 3-6, element 3 combined with one or more of elements 4-6, and combinations of two or more of elements 4-6.
[0149] A second non-limiting exemplary embodiment is a PP-polyamide produced according to the method of the first non-limiting exemplary embodiment (optionally including one or more of elements 1-6).
[0150] A third non-limiting exemplary embodiment includes functionalizing metal oxide particles attached to pigment particles with silica particles having a carboxylic acid (including terminal, pendant, or both terminal and pendant such groups) surface treatment to produce a surface treated pigment having pendant carboxylic acids, converting the pendant carboxylic acids to pendant acid chlorides, and reacting the pendant acid chlorides with polyamides to obtain pigment-pendant polyamides (PP-polyamides).A third non-limiting exemplary embodiment is element 7, wherein the metal oxide particles include one or more selected from the group consisting of titanium dioxide, titanium suboxide, titanium oxynitride, Al2O3, Fe2O3, Fe3O4, SnO2, Cr2O3, ZnO, CuO, NiO, zirconium oxide, and titanium iron oxide; element 7; and element 8, wherein the pigment particles include one or more selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, needle pigments, CaSO4, iron oxide, chromium oxide, carbon black, metal effect pigments, optically transparent pigments, and / or other pigments. Element 8 and Element 9, wherein the silica particles having a carboxylic acid surface treatment include one or more selected from the group consisting of 3-aminopropyl-(3-oxobutane) acid functionalized silica, 3-propylsulfonic acid functionalized silica gel, propyl carboxylic acid functionalized silica, triaminetetraacetic acid functionalized silica gel, propionyl chloride functionalized silica gel, 3-carboxypropyl functionalized silica gel, aminomethylphosphonic acid (AMPA) functionalized silica gel, and 1,4,7,10-tetraazacyclododecane- 1,4,7,10-tetraacetic acid (DOTA) functionalized silica gel; wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecane amide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,1 4, nylon 12, semi-aromatic polyamide, aromatic polyamide, any copolymer thereof, and any combination thereof; element 10, element 11, wherein the reaction of the pendant acid chloride with the polyamide comprises melt mixing the pigment particles having pendant acid chloride functionality with the polyamide for 15 minutes to about 1 hour at about 125° C. to about 250° C.; and element 12, wherein the weight ratio of pigment to polyamide is from about 1:10 to about 1:1000.Examples of combinations include, but are not limited to, element 7 combined with one or more of elements 8-12, element 8 combined with one or more of elements 9-12, element 9 combined with one or more of elements 10-12, and combinations of two or more of elements 10-12.
[0151] A fourth non-limiting exemplary embodiment is a PP-polyamide produced according to the method of the third non-limiting exemplary embodiment (optionally including one or more of elements 7-12).
[0152] A fifth non-limiting exemplary embodiment is a composition comprising a polyamide having a pigment pendant from the backbone chain of the polyamide, the pigment comprising metal oxide particles on the surface of the pigment particle. A third non-limiting exemplary embodiment is element 13, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacamide, polyundecane amide, polydodecane amide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, copolymers of any of these, and any combination thereof; element 13; element 14, wherein the weight ratio of pigment to polyamide is from about 1:10 to about 1:1000; element 15, wherein the pigment particles are one or more selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, acicular pigments, CaSO4, iron oxide, chromium oxide, carbon black, metallic effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
[0153] A sixth non-limiting exemplary embodiment is an object comprising the composition of the fifth non-limiting exemplary embodiment (optionally including one or more of elements 13-15), which can be produced by the first or third non-limiting exemplary embodiment.
[0154] A seventh non-limiting exemplary embodiment is a method comprising: depositing particles on a surface in a particular shape, where upon deposition the particles comprise the composition of the fifth non-limiting exemplary embodiment (optionally including one or more of elements 13-15); and heating at least a portion of the particles to promote consolidation of the particles to form a consolidated body. Further, the particles of the seventh non-limiting exemplary embodiment are made of polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate, polyethylene terephthalate, polyethylene naphthalate, polytrimethylene terephthalate, polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethene, polyester, polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene, polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyetherketone, polyamideimide, polyetherimide, polyetherester, copolymers comprising polyether blocks and polyamide blocks, grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized polyolefins. In some embodiments, the thermoplastic polymer may further comprise a thermoplastic polymer selected from the group consisting of functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride, phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.
[0155] An eighth non-limiting exemplary embodiment is a method comprising: mixing a mixture comprising a polyamide, the polyamide having pigments pendant from the backbone chain of the polyamide (PP-polyamide), a carrier fluid immiscible with the PP-polyamide, and optionally an emulsion stabilizer, at a temperature above the melting point or softening temperature of the PP-polyamide and at a shear rate high enough to disperse the PP-polyamide in the carrier fluid; and cooling the mixture below the melting point or softening temperature of the PP-polyamide to form solidified particles, the solidified particles comprising the PP-polyamide and, if present, the emulsion stabilizer associated with an outer surface of the solidified particles.
[0156] A ninth non-limiting exemplary embodiment is a composition comprising solidified particles comprising a polyamide, the polyamide having pigments pendant from a backbone chain of the polyamide (PP-polyamide), the solidified particles having a circularity of about 0.90 to about 1.0.
[0157] Eighth and ninth exemplary embodiments are: Element 16, where the emulsion stabilizer is included in the mixture (or the solidified particles further include the emulsion stabilizer), and the emulsion stabilizer is associated with the outer surface of the solidified particles; Element 16, Element 17, and Element 16, where at least a portion of the solidified particles have voids that include the emulsion stabilizer at the void / polymer interface; Element 17, Element 18, and Element 17, where the voids include the carrier fluid; Element 18, Element 19, and Element 17, where the emulsion stabilizer includes nanoparticles, and the nanoparticles are embedded at the void / polymer interface; Element 19, Element 20, and Element 16, where the solidified particles further include elongated structures on the surfaces of the solidified particles, and the elongated structures are associated with the outer surface of the elongated structures. Element 20, Element 21, Element 16, the emulsion stabilizer forms a coating that covers less than 5% of the surface of the solidified particles, Element 21, Element 22, Element 16, the emulsion stabilizer forms a coating that covers at least 5% of the surface of the solidified particles, Element 22, Element 23, Element 16, the emulsion stabilizer forms a coating that covers at least 25% of the surface of the solidified particles, Element 23, Element 24, Element 16, the emulsion stabilizer forms a coating that covers at least 50% of the surface of the solidified particles, Element 24, Element 25, Element 16, the emulsion stabilizer is less than 0.5% of the PP-polyamide.Element 25, Element 26, and Element 16, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles having an average diameter of 1 nm to 500 nm; Element 26, Element 27, and Element 16, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles comprising oxide nanoparticles; Element 27, Element 28, and Element 16, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles comprising carbon black; Element 28, Element 29, and Element 16, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles comprising poly Element 29, Element 30, wherein the mixture further comprises a thermoplastic polymer that is not PP-polyamide (or the consolidated particles further comprise a thermoplastic polymer that is not PP-polyamide); Element 30, Element 31, wherein the mixture further comprises a polyamide of PP-polyamide but does not have a pigment pendant from the PP-polyamide (or the consolidated particles further comprise a polyamide of PP-polyamide but does not have a pigment pendant from the PP-polyamide); Element 31, Element 32, wherein the pigment is synthetic mica, natural mica, talc, sericite, Element 32, Element 33, wherein the polyamide is selected from the group consisting of kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, needle-shaped pigments, CaSO4, iron oxides, chromium oxides, carbon black, metal effect pigments, optically variable pigments, liquid crystal polymer pigments, holographic pigments, and any combination thereof; Element 33, Element 34, wherein the weight ratio of pigment to polyamide is from about 1:10 to about 1:1000; Element 34, Element 35, wherein the solidified particles have a D10 of from about 0.1 μm to about 125 μm, a D11 of from about 0.5 μm to about 125 μm, a D22 of from about 0.5 μm to about 125 μm, and a D3 of from about 0.5 μm to about 125 μm.Element 35 and Element 36 having a D50 of 5 μm to about 200 μm and a D90 of about 3 μm to about 300 μm, with D10 < D50 < D90; Element 36 and Element 37, wherein the solidified particles have a diameter span of about 0.2 to about 10; Element 37 and Element 38, wherein the solidified particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, with D10 < D50 < D90; Element 38 and Element 39, which is Element 37, wherein the solidified particles have a diameter span of about 1.0 to about 2.5; Element 39 and Element 40, wherein the solidified particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, with D10 < D50 < D90; Element 40 and Element 41, which is Element 39, wherein the solidified particles have a diameter span of about 0.6 to about 1.5; Element 41 and Element 42, wherein the solidified particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, with D10 < D50 < D90; Element 42 and Element 43, which is Element 41, wherein the solidified particles have a diameter span of about 0.2 to about 1.2; Element 43 and Element 44, wherein the solidified particles have a circularity of about 0.90 to about 1.0; Element 44, wherein the solidified particles have a Hausner ratio of about 1.0 to about 1.5, may include one or more of the above. Examples of combinations include, but are not limited to, Element 16 combined with one or more of Elements 17 - 19; Element 16 combined with one of Elements 20 - 24, optionally further combined with one or more of Elements 17 - 19; (optionally combined with one of Elements 20 - 24 and / or optionally combined with one or more of Elements 17 - 19,) Element 16 combined with one or more of Elements 25 - 29; (optionally combined with one or more of Elements 17 - 29,) Element 16 combined with one or more of Elements 30 - 44; a combination of two or more of Elements 30 - 34; one or more of Elements 30 - 34 combined with one or more of Elements 35 - 44; and Element 43 and / or Element 44 combined with one or more of Elements 35 - 42.
[0158] Further, an eighth non-limiting exemplary embodiment is element 45, wherein the PP-polyamide is present in the mixture at 5% to 60% by weight of the mixture; element 45, element 46, wherein the carrier fluid is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, paraffin, liquid petroleum jelly, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, fatty acid modified polysiloxanes, fatty alcohol modified polysiloxanes. Element 46, Element 47, wherein the silicone oil is selected from the group consisting of polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and any combination thereof; Element 47, Element 48, wherein the carrier fluid has a viscosity of 1000 cSt to 150,000 cSt at 25° C.; and Element 49, wherein the carrier fluid has a viscosity of 0.6 g / cm 3 ~1.5g / cm 3 Examples of combinations include, but are not limited to, one or more of elements 16-44 combined with one or more of elements 45-49, and two or more of elements 45-49.
[0159] section Section 1. A method comprising functionalizing metal oxide particles attached to pigment particles with a compound having an epoxy (including terminal, pendant, or both terminal and pendant such groups) to produce a surface treated pigment having a pendant epoxy, and reacting the pendant epoxy with a polyamide to obtain a pigment-pendant polyamide (PP-polyamide).
[0160] Section 2. The method of section 1, wherein the compound having the epoxide is selected from the group consisting of (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane and 1,3-bis(3-glycidyloxypropyl)tetramethylsiloxane, 2-(3,4 epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 5,6-epoxyhexyltriethoxysilane, and any combination thereof.
[0161] Section 3. The method of section 1, wherein the metal oxide particles comprise one or more selected from the group consisting of titanium dioxide, titanium suboxide, titanium oxynitride, Al2O3, Fe2O3, Fe3O4, SnO2, Cr2O3, ZnO, CuO, NiO, zirconium oxide, and titanium iron oxide.
[0162] Section 4. The method of section 1, wherein the pigment particles comprise one or more selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, acicular pigments, CaSO4, iron oxides, chromium oxides, carbon black, metallic effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
[0163] Section 5. The method of section 1, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecanamide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, copolymers of any of these, and any combination thereof.
[0164] Section 6. The method according to section 1, wherein the reaction of the pendant epoxy with the polyamide is carried out at about 70°C to about 200°C.
[0165] Clause 7. The method according to clause 1, wherein the weight ratio of the pigment to the polyamide is from about 1:10 to about 1:1000.
[0166] Section 8. Functionalizing metal oxide particles attached to pigment particles with silica particles having a carboxylic acid (including terminal, pendant, or both terminal and pendant such groups) surface treatment to produce a surface treated pigment having pendant carboxylic acid, converting the pendant carboxylic acid to a pendant acid chloride, and reacting the pendant acid chloride with a polyamide to obtain a pigment-pendant polyamide (PP-polyamide).
[0167] Section 9. The method of section 8, wherein the metal oxide particles comprise one or more selected from the group consisting of titanium dioxide, titanium suboxide, titanium oxynitride, Al2O3, Fe2O3, Fe3O4, SnO2, Cr2O3, ZnO, CuO, NiO, zirconium oxide, and titanium iron oxide.
[0168] Clause 10. The method of clause 8, wherein the pigment particles comprise one or more selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, acicular pigments, CaSO4, iron oxides, chromium oxides, carbon black, metallic effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
[0169] Clause 11. The method of clause 8, wherein the silica particles having a carboxylic acid surface treatment comprise one or more selected from the group consisting of 3-aminopropyl-(3-oxobutane) acid functionalized silica, 3-propylsulfonic acid functionalized silica gel, propyl carboxylic acid functionalized silica, triaminetetraacetic acid functionalized silica gel, propionyl chloride functionalized silica gel, 3-carboxypropyl functionalized silica gel, aminomethylphosphonic acid (AMPA) functionalized silica gel, and 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) functionalized silica gel.
[0170] Clause 12. The method of clause 8, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecanamide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, copolymers of any of these, and any combination thereof.
[0171] Clause 13. The method of clause 8, wherein said reacting said pendant acid chloride with said polyamide comprises melt mixing said pigment particles functionalized with said pendant acid chloride with said polyamide for 15 minutes to about 1 hour at about 125°C to about 250°C.
[0172] Clause 14. The method according to clause 8, wherein the weight ratio of the pigment to the polyamide is from about 1:10 to about 1:1000.
[0173] Section 15. A composition comprising a polyamide, the polyamide having a pigment pendant from a backbone chain of the polyamide, the pigment comprising metal oxide particles on a surface of the pigment particle.
[0174] Clause 16. The composition of clause 15, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecane amide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, copolymers of any of these, and any combination thereof.
[0175] Clause 17. The composition according to clause 15, wherein the weight ratio of the pigment to the polyamide is from about 1:10 to about 1:1000.
[0176] Clause 18. The composition of clause 15, wherein the pigment particles comprise one or more selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, acicular pigments, CaSO4, iron oxides, chromium oxides, carbon black, metallic effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
[0177] Section 19. An article comprising the composition described in Section 15.
[0178] Clause 20. A method comprising: depositing particles on a surface in a particular shape, the particles comprising the polyamide of any one of claims 15 to 18 as deposited; and heating at least a portion of the particles to promote consolidation of the particles to form a consolidated body.
[0179] Section 21. The particles are selected from the group consisting of polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate, polyethylene terephthalate, polyethylene naphthalate, polytrimethylene terephthalate, polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester, polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene, polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyetherketone, polyamideimide, polyetherimide, polyetherester, copolymers containing polyether blocks and polyamide blocks, grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl copolymers. 21. The method of claim 20, further comprising a thermoplastic polymer selected from the group consisting of a vinyl monomer polymer, a functionalized or non-functionalized ethylene / alkyl (meth)acrylate, a functionalized or non-functionalized (meth)acrylic acid polymer, a functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymer, an ethylene / vinyl monomer / carbonyl terpolymer, an ethylene / alkyl (meth)acrylate / carbonyl terpolymer, a methyl methacrylate-butadiene-styrene type core-shell polymer, a polystyrene-block-polybutadiene-block-poly(methyl methacrylate) block terpolymer, a chlorinated or chlorosulfonated polyethylene, a polyvinylidene fluoride, a phenolic resin, a poly(ethylene / vinyl acetate), a polybutadiene, a polyisoprene, a styrenic block copolymer, a polyacrylonitrile, a silicone, and any combination thereof.
[0180] Section 22. A method comprising: mixing a mixture comprising a polyamide, the polyamide having pigments pendant from the backbone chain of the polyamide (PP-polyamide), a carrier fluid immiscible with the PP-polyamide, and optionally an emulsion stabilizer, at a temperature above the melting point or softening temperature of the PP-polyamide and at a shear rate high enough to disperse the PP-polyamide in the carrier fluid; and cooling the mixture below the melting point or softening temperature of the PP-polyamide to form solidified particles, the solidified particles comprising the PP-polyamide and, if present, the emulsion stabilizer associated with the outer surface of the solidified particles.
[0181] Clause 23. The method of clause 22, wherein the emulsion stabilizer is included in the mixture, and the emulsion stabilizer is associated with an outer surface of the solidified particles.
[0182] Clause 24. The method of clause 23, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles being embedded in the outer surface of the solidified particles.
[0183] Clause 25. The method of clause 22, wherein the mixture further comprises a thermoplastic polymer that is not the PP-polyamide.
[0184] Clause 26. The method of clause 22, wherein the mixture further comprises the polyamide of the PP-polyamide, but does not have pigment pendants from the PP-polyamide.
[0185] Clause 27. The method of clause 22, wherein the pigment is selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, acicular pigments, CaSO4, iron oxides, chromium oxides, carbon black, metallic effect pigments, optically variable pigments, liquid crystal polymer pigments, holographic pigments, and any combination thereof.
[0186] Clause 28. The method of clause 22, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecanamide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, copolymers of any of these, and any combination thereof.
[0187] Clause 29. The method of clause 22, wherein the weight ratio of the pigment to the polyamide is from about 1:10 to about 1:1000.
[0188] Clause 30. The method of clause 22, wherein at least a portion of the solidified particles have voids that contain the emulsion stabilizer at the void / polymer interface.
[0189] Clause 31. The method of clause 30, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles being embedded at the void / polymer interface.
[0190] Clause 32. The method of clause 30, wherein the void contains the carrier fluid.
[0191] Clause 33. The method of clause 22, wherein the solidified particles further comprise elongated structures on the surface of the solidified particles, the elongated structures comprising the PP-polyamide having the emulsion stabilizer associated with an outer surface of the elongated structures.
[0192] Clause 34. The method of clause 22, wherein the emulsion stabilizer is included, and the emulsion stabilizer forms a coating that covers less than 5% of the surface of the solidified particles.
[0193] Clause 35. The method of clause 22, wherein the emulsion stabilizer is included, and the emulsion stabilizer forms a coating that covers at least 5% of the surface of the solidified particles.
[0194] Clause 36. The method of clause 22, wherein the emulsion stabilizer is included, and the emulsion stabilizer forms a coating that covers at least 25% of the surface of the solidified particles.
[0195] Clause 37. The method of clause 22, wherein the emulsion stabilizer is included, and the emulsion stabilizer forms a coating that covers at least 50% of the surface of the solidified particles.
[0196] Clause 38. The method of clause 22, wherein the PP-polyamide is present in the mixture at 5% to 60% by weight of the mixture.
[0197] Clause 39. The method of clause 22, wherein the emulsion stabilizer is included, and the emulsion stabilizer is present in the mixture at 0.05% to 5% by weight of the PP-polyamide.
[0198] Clause 40. The method of clause 22, wherein the emulsion stabilizer comprises the nanoparticles, the nanoparticles having an average diameter of 1 nm to 500 nm.
[0199] Clause 41. The method of clause 22, wherein the carrier fluid is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, paraffin, liquid petroleum jelly, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, fatty acid modified polysiloxanes, fatty alcohol modified polysiloxanes, polyoxyalkylene modified polysiloxanes, and any combination thereof.
[0200] Clause 42. The method according to clause 41, wherein the silicone oil is selected from the group consisting of polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and any combination thereof.
[0201] Clause 43. The method of clause 22, wherein the carrier fluid has a viscosity of between 1000 cSt and 150,000 cSt at 25°C.
[0202] Clause 44. The carrier fluid has a density of 0.6 g / cm 3 ~1.5g / cm 3 23. The method of claim 22, wherein the density of the
[0203] Clause 45. The method of clause 22, wherein the mixing is performed in an extruder.
[0204] Section 46. Mixing is carried out in a stirring reactor by the method described in Section 22.
[0205] Section 47. The mixture further contains a surfactant by the method described in Section 22.
[0206] Section 48. The solidified particles have a D10 of about 0.1 μm to about 125 μm, a D50 of about 0.5 μm to about 200 μm, and a D90 of about 3 μm to about 300 μm, with D10 < D50 < D90, by the method described in Section 22.
[0207] Section 49. The solidified particles have a diameter span of about 0.2 to about 10, by the method described in Section 22.
[0208] Section 50. The solidified particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, with D10 < D50 < D90, by the method described in Section 22.
[0209] Section 51. The solidified particles have a diameter span of about 1.0 to about 2.5, by the method described in Section 50.
[0210] Section 52. The solidified particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, with D10 < D50 < D90, by the method described in Section 22.
[0211] Section 53. The solidified particles have a diameter span of about 0.6 to about 1.5, by the method described in Section 52.
[0212] Section 54. The solidified particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, with D10 < D50 < D90, by the method described in Section 22.
[0213] Section 55. The solidified particles have a diameter span of about 0.2 to about 1.2, by the method described in Section 54.
[0214] Clause 56. The method of clause 22, wherein the solidified particles have a circularity of about 0.90 to about 1.0.
[0215] Clause 57. The method of clause 22, wherein the solidified particles have a Hausner ratio of about 1.0 to about 1.5.
[0216] Clause 58. The method of clause 22, wherein the emulsion stabilizer comprises nanoparticles, and the nanoparticles comprise oxide nanoparticles.
[0217] Clause 59. The method of clause 22, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles comprising carbon black.
[0218] Clause 60. The method of clause 22, wherein the emulsion stabilizer comprises nanoparticles, and the nanoparticles comprise polymeric nanoparticles.
[0219] Clause 61. A composition comprising particles comprising a polyamide having a pigment pendant from a backbone chain of the polyamide (PP-polyamide), the particles having a circularity of about 0.90 to about 1.0.
[0220] Clause 62. The composition of clause 61, wherein the particles further comprise a thermoplastic polymer that is not the PP-polyamide.
[0221] Clause 63. The composition of clause 61, wherein the particles further comprise the polyamide of the PP-polyamide, but do not have pigment pendants from the PP-polyamide.
[0222] Clause 64. The composition of clause 61, wherein the particles further comprise an emulsion stabilizer associated with the outer surface of the particles.
[0223] Clause 65. The composition of clause 61, wherein at least a portion of the particles have voids that contain the emulsion stabilizer at the void / polymer interface.
[0224] Section 66. The composition according to Section 65, wherein the emulsifying stabilizer contains nanoparticles, and the nanoparticles are embedded in the void / polymer interface.
[0225] Section 67. The composition according to Section 65, wherein the void contains the carrier fluid.
[0226] Section 68. The composition according to Section 61, wherein the particles further include elongated structures on the surface of the particles, and the elongated structures include the PP-polyamide having the emulsifying stabilizer associated with the outer surface of the elongated structures.
[0227] Section 69. The composition according to Section 61, wherein the emulsifying stabilizer forms a coating that covers less than 5% of the surface of the solidified particles.
[0228] Section 70. The composition according to Section 61, wherein the emulsifying stabilizer forms a coating that covers at least 5% of the surface of the solidified particles.
[0229] Section 71. The composition according to Section 61, wherein the emulsifying stabilizer forms a coating that covers at least 25% of the surface of the solidified particles.
[0230] Section 72. The composition according to Section 61, wherein the emulsifying stabilizer forms a coating that covers at least 50% of the surface of the solidified particles.
[0231] Section 73. The composition according to Section 61, wherein the emulsifying stabilizer contains nanoparticles having an average diameter of 1 nm to 500 nm.
[0232] Section 74. The composition according to Section 61, wherein the solidified particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, and D10 < D50 < D90.
[0233] Section 75. The composition according to Section 61, wherein the solidified particles have a diameter span of about 0.2 to about 10.
[0234] Section 76. The cured particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, with D10 < D50 < D90, and the composition according to Section 61.
[0235] Section 77. The cured particles have a diameter span of about 1.0 to about 2.5, and the composition according to Section 76.
[0236] Section 78. The cured particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, with D10 < D50 < D90, and the composition according to Section 61.
[0237] Section 79. The cured particles have a diameter span of about 0.6 to about 1.5, and the composition according to Section 78.
[0238] Section 80. The cured particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, with D10 < D50 < D90, and the composition according to Section 61.
[0239] Section 81. The cured particles have a diameter span of about 0.2 to about 1.2, and the composition according to Section 80.
[0240] Section 82. The cured particles have a Hausner ratio of about 1.0 to about 1.5, and the composition according to Section 61.
[0241] Section 83. A method comprising depositing the composition according to Section 61, optionally in combination with other thermoplastic polymer particles, on a surface in a specific shape, and upon deposition, heating at least a portion of the particles to promote consolidation of the particles to form a consolidated body.
[0242] Unless otherwise indicated, all numbers expressing quantities of ingredients, properties such as molecular weight, reaction conditions, and the like used in this specification and the related claims are to be understood in all instances as being modified by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending upon the desired properties believed to be obtained by the implementation of the present invention. At the very least, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0243] One or more exemplary implementations incorporating one or more inventive elements are presented herein. For clarity, not all features of a physical implementation are described or shown in this application. It is understood that in developing a physical embodiment incorporating one or more elements of the present invention, numerous implementation-specific decisions must be made to achieve the developer's goals, such as implementation and compliance with system-related, business-related, government-related, and other constraints, which may change from time to time. Although the developer's efforts may be time-consuming, such efforts would nevertheless be routine for those of ordinary skill in the art having the benefit of this disclosure.
[0244] Although the compositions and methods are described herein in terms "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.
[0245] To facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should not be read to limit or define the scope of the present invention. EXAMPLES
[0246] Prophetic Example 1: IRIODIN® 100 Silver Pearl pigment reacted with (3-glycidyloxypropyl)trimethoxysilane and crosslinked with polyamide resin in solution To a 2 liter glass reactor equipped with an overhead mechanical stirrer and heating mantle is added 100 g of IRIODIN® 100 Silver Pearl pigment (available from E. Merck KGaA, Darmstadt) suspended in 900 mL of deionized water and heated with vigorous stirring to 40° C. The suspension is adjusted to pH 3.3 with 2.5% hydrochloric acid and the temperature is increased to 75° C.
[0247] Then, 3.0 g of (3-glycidyloxypropyl)trimethoxysilane (available from Millipore Sigma) is added over 10 minutes and the pH is kept constant with a 2.5% hydrochloric acid solution. After addition is complete, stirring is continued for 2 hours at 75° C., during which time the silane hydrolyzes and the resulting silanols become associated with the inorganic pigment surface.
[0248] The reaction temperature is then maintained at 75° C. while the reaction system is adjusted to pH 8.0 very slowly over 1 hour using 2.5% sodium hydroxide solution, during which time the condensation reaction occurs and the resulting siloxane bonds bond to the pigment surface leaving unreacted epoxy end groups for subsequent functionalization. Stirring is continued for an additional hour at 75° C. to complete the reaction, at which point the pH drops to 7.0. The product is filtered off using vacuum filtration, washed with deionized water, and dried at 140° C. for approximately 16 hours.
[0249] Subsequently, 100 g of polyamide resin, such as nylon 6,6, is dissolved in N-methyl-2-pyrrolidone (NMP) with vigorous stirring. To this mixture, 10 g of epoxide-functionalized IRIODIN® 100 Silver Pearl pigment is added from above, and the continuously stirred reaction mixture is raised to 150° C. for 2 hours to promote a curing reaction between the amino functional groups of the polyamide resin and the pendant glycidyloxypropyl (epoxide) groups coating the surface of the IRIODIN® 100 Silver Pearl pigment. After the polyamide resin has cured and coated the suspended IRIODIN® 100 Silver Pearl pigment, the solvent is removed by filtering the particles using vacuum filtration, and the material is thoroughly dried in a vacuum oven for 24 hours. A portion of this mixture is then mixed with non-pigment pendant polyamide in a Haake reaction with PDMS to form particles.
[0250] 2.5 g of IRIODIN® 100 Silver Pearl pigment-pendant crosslinked by polyamide resin on the pigment surface and 27.5 g of nylon 6,6 are melt mixed with 150 g of polydimethylsiloxane (PDMS) with a specific viscosity of 60,000 by hot melt emulsification in a Haake mixer fitted with a 300 mL mixing vessel. The mixer is heated to 230° C. and mixed at 200 rpm for 20 minutes. The mixture is then discharged from the Haake onto a cold surface resulting in rapid quench cooling. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The PP-polyamide particles are washed three times with 1000 mL of ethyl acetate. The PP-polyamide particles are then air-dried overnight in an aluminum pan in a fume hood. If desired, the dried PP-polyamide particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. D50 (μm) is predicted to be about 50 μm with a span of about 0.85.
[0251] Prophetic Example 2: BLONDIEE® Metallic Super Gold Pigment Reacted with (3-Glycidyloxypropyl) Trimethoxysilane and Crosslinked in Situ with Polyamide Resin To a 2 liter glass reactor equipped with an overhead mechanical stirrer and heating mantle is added 100 g of BLONDIEE® Metallic Super Gold pigment, product code N-2002 S (available from Creation of Quality Value Company Ltd.), suspended in 900 mL of deionized water and heated with vigorous stirring to 40° C. The suspension is adjusted to pH 3.3 with 2.5% hydrochloric acid and the temperature is increased to 75° C.
[0252] Then, 3.0 g of (3-glycidyloxypropyl)trimethoxysilane (available from Millipore Sigma) is added over 10 minutes and the pH is kept constant with a 2.5% hydrochloric acid solution. After addition is complete, stirring is continued for 2 hours at 75° C., during which time the silane hydrolyzes and the resulting silanols become associated with the inorganic pigment surface.
[0253] The reaction temperature is then maintained at 75° C. while the reaction system is adjusted to pH 8.0 very slowly over 1 hour using 2.5% sodium hydroxide solution, during which time the condensation reaction occurs and the resulting siloxane bonds bond to the pigment surface leaving unreacted epoxy end groups for subsequent functionalization. Stirring is continued for an additional hour at 75° C. to complete the reaction, at which point the pH drops to 7.0. The product is filtered off using vacuum filtration, washed with deionized water, and dried at 140° C. for approximately 16 hours.
[0254] Subsequently, 50 g of polyamide resin, such as nylon 6,6, is melt mixed with 10 g of the above epoxide surface functionalized mica pigment Blondiee® Metallic Super Gold in a Haake mixer at 150° C.-200° C. for 20-30 minutes to promote the crosslinking reaction of the epoxide with the amino groups of the polyamide resin. The resulting pigment-pendant polyamide resin concentrate is discharged from the Haake mixer, cooled, and ground into a fine powder for subsequent incorporation into micrometer-sized particles of pigmented polyamide.
[0255] 1.5 g of BLONDIEE® Metallic Super Gold pigment-polyamide resin on the pendant crosslinked pigment surface and 28.5 g of nylon 6,6 are melt mixed with 150 g of polydimethylsiloxane (PDMS) with a specific viscosity of 30,000 by hot melt emulsification in a Haake mixer fitted with a 300 mL mixing vessel. The mixer is heated to 230° C. and mixed at 200 rpm for 20 minutes.
[0256] The mixture is then discharged from the Haake onto a cold surface resulting in rapid quench cooling. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 1000 mL of ethyl acetate. The particles are then air-dried overnight in an aluminum pan in a fume hood. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 65 μm with a span of about 1.20.
[0257] Prophetic Example 3: REFLEX® 100 Sparkle Violet Pigment Reacted with (3-Glycidyloxypropyl)trimethoxysilane and Crosslinked with Polyamide Resin in Solution To a 2 liter glass reactor equipped with an overhead mechanical stirrer and heating mantle is added 100 g of REFLEX® 100 Sparkle Violet R-706E pigment (available from Creation of Quality Value Company Ltd.) suspended in 900 mL of deionized water and heated with vigorous stirring to 40° C. The suspension is adjusted to pH 3.3 with 2.5% hydrochloric acid and the temperature is increased to 75° C.
[0258] Then, 3.0 g of (3-glycidyloxypropyl)trimethoxysilane (available from Millipore Sigma) is added over 10 minutes and the pH is kept constant with a 2.5% hydrochloric acid solution. After addition is complete, stirring is continued for 2 hours at 75° C., during which time the silane hydrolyzes and the resulting silanols become associated with the inorganic pigment surface.
[0259] The reaction temperature is then maintained at 75° C. while the reaction system is adjusted to pH 8.0 very slowly over 1 hour using 2.5% sodium hydroxide solution, during which time the condensation reaction occurs and the resulting siloxane bonds bond to the pigment surface leaving unreacted epoxy end groups for subsequent functionalization. Stirring is continued for an additional hour at 75° C. to complete the reaction, at which point the pH drops to 7.0. The product is filtered off using vacuum filtration, washed with deionized water, and dried at 140° C. for approximately 16 hours.
[0260] Subsequently, 100 g of polyamide resin, such as nylon 6,6, is dissolved in N-methyl-2-pyrrolidone (NMP) with vigorous stirring. To this mixture, 10 g of epoxide-functionalized REFLEX® 100 Sparkle Violet R-706E pigment is added from above, and the continuously stirred reaction mixture is raised to 150° C. for 2 hours to promote a curing reaction between the amino functional groups of the polyamide resin and the pendant glycidyloxypropyl (epoxide) groups coating the surface of the REFLEX® 100 Sparkle Violet R-706E pigment. After the polyamide resin has cured and coated the suspended REFLEX® 100 Sparkle Violet R-706E pigment, the solvent is removed by filtering the particles using vacuum filtration, and the material is thoroughly dried in a vacuum oven for 24 hours. A portion of this mixture is then mixed with non-pigment pendant polyamide in a Haake reaction with PDMS to form particles.
[0261] 50 g of REFLEX® 100 Sparkle Violet R-706E pigment-pendant crosslinked on the pigment surface by polyamide resin and 550 g of nylon 6,6 are melt mixed with 2000 g of polydimethylsiloxane (PDMS) with a specific viscosity of 10,000 by hot melt emulsification in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The polymer pellets are first added to the extruder, brought to a temperature of 230° C. and 900 rpm, and then the preheated carrier fluid with AEROSIL® R812S silica nanoparticles (1.1 wt % relative to PP-polyamide) dispersed therein is added to the molten polymer in the extruder.
[0262] The mixture is then discharged into a container and cooled to room temperature over several hours. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 2000 mL of ethyl acetate. The particles are then dried overnight in a vacuum oven at ambient temperature. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 75 μm with a span of about 1.30.
[0263] Prophetic Example 4: Reflex® Glitter Blue R-781E Pigment Reacted with (3-Glycidyloxypropyl) Trimethoxysilane and Crosslinked in Situ with Polyamide Resin To a 2 liter glass reactor equipped with an overhead mechanical stirrer and heating mantle is added 100 g of Reflex® Glitter Blue pigment, product code R-781E (available from Creation of Quality Value Company Ltd.), suspended in 900 mL of deionized water and heated with vigorous stirring to 40° C. The suspension is adjusted to pH 3.3 with 2.5% hydrochloric acid and the temperature is increased to 75° C.
[0264] Then, 3.0 g of (3-glycidyloxypropyl)trimethoxysilane (available from Millipore Sigma) is added over 10 minutes and the pH is kept constant with a 2.5% hydrochloric acid solution. After addition is complete, stirring is continued for 2 hours at 75° C., during which time the silane hydrolyzes and the resulting silanols become associated with the inorganic pigment surface.
[0265] The reaction temperature is then maintained at 75° C. while the reaction system is adjusted to pH 8.0 very slowly over 1 hour using 2.5% sodium hydroxide solution, during which time the condensation reaction occurs and the resulting siloxane bonds bond to the pigment surface leaving unreacted epoxy end groups for subsequent functionalization. Stirring is continued for an additional hour at 75° C. to complete the reaction, at which point the pH drops to 7.0. The product is filtered off using vacuum filtration, washed with deionized water, and dried at 140° C. for approximately 16 hours.
[0266] Subsequently, 50 g of polyamide resin, such as nylon 6,6, is melt mixed with 10 g of the above epoxide surface functionalized mica pigment Reflex® GlitBlue R-871E in a Haake mixer at 150° C.-200° C. for 20-30 minutes to promote the crosslinking reaction of the epoxide with the amino groups of the polyamide resin. The resulting pigment-pendant polyamide resin concentrate is discharged from the Haake mixer, cooled, and ground into a fine powder for subsequent incorporation into micrometer-sized particles of pigmented polyamide.
[0267] 30 g of REFLEX® Glitter Blue R-871E pigment-pendant crosslinked polyamide resin on the pigment surface and 570 g of nylon 6,6 are melt mixed with 2000 g of polydimethylsiloxane (PDMS) with a specific viscosity of 10,000 by hot melt emulsification in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The polymer pellets are first added to the extruder at a temperature of 230° C. and 900 rpm, and then the preheated carrier fluid with AEROSIL® R812S silica nanoparticles (1.1 wt % relative to PP-polyamide) dispersed therein is added to the molten polymer in the extruder.
[0268] The mixture is then discharged into a container and cooled to room temperature over several hours. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 2000 mL of ethyl acetate. The particles are then dried overnight in a vacuum oven at ambient temperature. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 65 μm with a span of about 1.10.
[0269] Prophetic Example 5: IRIODIN® 100 Silver Pearl pigment reacted with 3-aminopropyl (3-oxobutanoic) acid functionalized silica nanoparticles and crosslinked in situ with polyamide resin To a 2 liter glass reactor equipped with an overhead mechanical stirrer and a heating mantle, 100 g of IRIODIN® 100 Silver Pearl pigment (available from E. Merck KGaA, Darmstadt, Germany) suspended in 100 mL of 3-aminopropyl (3-oxobutanoic) acid functionalized silica nanoparticles (available from Millipore Sigma) as a colloidal dispersion at 2.5 wt % loading in 900 mL of deionized water and dimethylformamide (DMF) is added. The mixture is heated to 40° C. with vigorous stirring for 4 hours to promote the adsorption of the silica nanoparticles onto the surface of the pigment. The suspension is cooled to room temperature and filtered to remove the water and DMF solvent. The functionalized pigment particles with free carboxylic acid functional groups are dried in a vacuum oven at 40° C. for 24 hours to produce a functionalized pigment powder.
[0270] A clear, viscous stock solution (1.5 molar) of thionyl chloride (5.46 mL, 0.075 mol) and benzotriazole (8.93 g, 0.075 mol) in 50 mL of dry methylene chloride was prepared with mixing at room temperature. A portion of this solution (1.25 mmol) was added slowly to convert the pendant carboxylic acid functional groups on the surface of the mica pigment to acid chlorides, allowing curing by the aminopolyamide groups in the polyamide resin.
[0271] Dry mica pigment IRIODIN® 100 Silver Pearl (approximately 110 g) functionalized with surface carboxylic acid is suspended in 500 mL of dry methylene chloride with constant stirring. To this mixture, 20 mL of thionyl chloride-benzotriazole mixture is slowly added over 30 minutes at room temperature. As the reaction proceeds, the benzotriazole hydrochloride salt begins to precipitate out of solution, indicating conversion of the carboxylic acid to the acid chloride. The reaction mixture is mixed for an additional 30 minutes, and then the mixture is filtered to remove the solvent, thoroughly washed with water, and then dried in a vacuum oven for 24 hours.
[0272] Subsequently, 50 g of a polyamide resin, such as nylon 6,6, is mixed with 10 g of the melt mixed acid chloride surface functionalized mica pigment IRIODIN® 100 Silver Pearl in a Haake mixer at 150° C.-200° C. for 20-30 minutes to promote the crosslinking reaction of the acid chloride with the amino groups of the polyamide resin. The resulting pigment-pendant polyamide resin concentrate is discharged from the Haake mixer, cooled, and ground into a fine powder for subsequent incorporation of the pigmented polyamide into micrometer-sized particles.
[0273] 1.5 g of IRIODIN® 100 Silver Pearl pigment-polyamide resin on the pendant crosslinked pigment surface and 28.5 g of nylon 6,6 are melt mixed with 150 g of polydimethylsiloxane (PDMS) of specific viscosity 30,000 containing AEROSIL® R812S silica nanoparticles dispersed therein (0.75 wt.% with respect to PP-polyamide) by hot melt emulsification in a Haake mixer fitted with a 300 mL mixing vessel. The mixer is heated to 230° C. and mixed at 200 rpm for 15 minutes.
[0274] The mixture is then discharged from the Haake onto a cold surface resulting in rapid quench cooling. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 1000 mL of ethyl acetate. The particles are then air-dried overnight in an aluminum pan in a fume hood. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 55 μm with a span of about 1.10.
[0275] Prophetic Example 6: BLONDIEE® Metallic Super Gold Pigment Reacted with 3-Aminopropyl (3-Oxobutanoic) Acid Functionalized Silica Nanoparticles and Crosslinked in Situ with Polyamide Resin To a 2 liter glass reactor equipped with an overhead mechanical stirrer and a heating mantle, 100 g of BLONDIEE® Metallic Super Gold (available from Creation of Quality Value Company Ltd.) suspended in 100 mL of 3-aminopropyl (3-oxobutanoic acid) acid functionalized silica nanoparticles (available from Millipore Sigma) as a colloidal dispersion at 2.5 wt % loading in 900 mL of deionized water and DMF is added. The mixture is heated to 40° C. with vigorous stirring for 4 hours to promote the adsorption of the silica nanoparticles onto the surface of the pigment. The suspension is cooled to room temperature and filtered to remove the water and DMF solvent. The functionalized pigment particles with free carboxylic acid functional groups are dried in a vacuum oven at 40° C. for 24 hours to produce a functionalized pigment powder.
[0276] A clear, viscous stock solution (1.5 molar) of thionyl chloride (5.46 mL, 0.075 mol) and benzotriazole (8.93 g, 0.075 mol) in 50 mL of dry methylene chloride was prepared with mixing at room temperature. A portion of this solution (1.25 mmol) was added slowly to convert the pendant carboxylic acid functional groups on the surface of the mica pigment to acid chlorides, allowing curing by the aminopolyamide groups in the polyamide resin.
[0277] Dry mica pigment functionalized with surface carboxylic acid, BLONDIEE® Metallic Super Gold (approximately 110 g), is suspended in 500 mL of dry methylene chloride with constant stirring. To this mixture, 20 mL of the thionyl chloride-benzotriazole mixture is slowly added over 30 minutes at room temperature. As the reaction proceeds, the benzotriazole hydrochloride salt begins to precipitate out of solution, indicating conversion of the carboxylic acid to the acid chloride. The reaction mixture is mixed for an additional 30 minutes, and then the mixture is filtered to remove the solvent, thoroughly washed with water, and then dried in a vacuum oven for 24 hours.
[0278] Subsequently, 50 g of polyamide resin, such as nylon 6,6, is melt mixed with 10 g of the above acid chloride surface functionalized mica pigment Blondiee® Metallic Super Gold in a Haake mixer at 150° C.-200° C. for 20-30 minutes to promote the crosslinking reaction of the acid chloride with the amino groups of the polyamide resin. The resulting pigment-pendant polyamide resin concentrate is discharged from the Haake mixer, cooled, and ground into a fine powder for subsequent incorporation into micrometer-sized particles of pigmented polyamide.
[0279] 1.5 g of BLONDIEE® Metallic Super Gold pigment-polyamide resin on the pendant crosslinked pigment surface and 28.5 g of nylon 6,6 are melt mixed with 150 g of polydimethylsiloxane (PDMS) of specific viscosity 30,000 containing AEROSIL® R812S silica nanoparticles dispersed therein (1.00 wt.% with respect to PP-polyamide) by hot melt emulsification in a Haake mixer fitted with a 300 mL mixing vessel. The mixer is heated to 230° C. and mixed at 200 rpm for 15 minutes.
[0280] The mixture is then discharged from the Haake onto a cold surface resulting in rapid quench cooling. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 1000 mL of ethyl acetate. The particles are then air-dried overnight in an aluminum pan in a fume hood. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 50 μm with a span of about 0.95.
[0281] Prophetic Example 7: REFLEX® 100 Sparkle Violet Pigment Reacted with 3-Aminopropyl (3-Oxobutanoic) Acid Functionalized Silica Nanoparticles and Crosslinked in Situ with Polyamide Resin To a 2 liter glass reactor equipped with an overhead mechanical stirrer and a heating mantle, 100 g of REFLEX® 100 Sparkle Violet R-706E (available from Creation of Quality Value Company Ltd.) suspended in 100 mL of 3-aminopropyl (3-oxobutanoic acid) acid functionalized silica nanoparticles (available from Millipore Sigma) as a colloidal dispersion at 2.5 wt % loading in 900 mL of deionized water and DMF is added. The mixture is heated to 40° C. with vigorous stirring for 4 hours to promote the adsorption of the silica nanoparticles onto the surface of the pigment. The suspension is cooled to room temperature and filtered to remove the water and DMF solvent. The functionalized pigment particles with free carboxylic acid functional groups are dried in a vacuum oven at 40° C. for 24 hours to produce a functionalized pigment powder.
[0282] A clear, viscous stock solution (1.5 molar) of thionyl chloride (5.46 mL, 0.075 mol) and benzotriazole (8.93 g, 0.075 mol) in 50 mL of dry methylene chloride was prepared with mixing at room temperature. A portion of this solution (1.25 mmol) was added slowly to convert the pendant carboxylic acid functional groups on the surface of the mica pigment to acid chlorides, allowing curing by the aminopolyamide groups in the polyamide resin.
[0283] The dried mica pigment REFLEX® 100 Sparkle Violet R-706E (approximately 110 g) functionalized with surface carboxylic acid is suspended in 500 mL of dry methylene chloride with constant stirring. To this mixture, 20 mL of the thionyl chloride-benzotriazole mixture is slowly added over 30 minutes at room temperature. As the reaction proceeds, the benzotriazole hydrochloride salt begins to precipitate out of solution, indicating conversion of the carboxylic acid to the acid chloride. The reaction mixture is mixed for an additional 30 minutes, and then the mixture is filtered to remove the solvent and thoroughly washed with water before being dried in a vacuum oven for 24 hours.
[0284] Subsequently, 50 g of a polyamide resin, such as nylon 6,6, is melt mixed with 10 g of the above acid chloride surface functionalized mica pigment, Reflex® 100 Sparkle Violet R-706E, in a Haake mixer at 150° C.-200° C. for 20-30 minutes to promote the crosslinking reaction of the acid chloride with the amino groups of the polyamide resin. The resulting pigment-pendant polyamide resin concentrate is discharged from the Haake mixer, cooled, and ground into a fine powder for subsequent incorporation into micrometer-sized particles of pigmented polyamide.
[0285] 30 g of REFLEX® 100 Sparkle Violet R-706E pigment-pendant crosslinked polyamide resin on the pigment surface and 570 g of nylon 6,6 are melt mixed with 2000 g of polydimethylsiloxane (PDMS) with a specific viscosity of 20,000 by hot melt emulsification in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The polymer pellets are first added to the extruder at a temperature of 230° C. and 1100 rpm, and then the preheated carrier fluid with AEROSIL® R812S silica nanoparticles (1.1 wt % relative to PP-polyamide) dispersed therein is added to the molten polymer in the extruder.
[0286] The mixture is then discharged into a container and cooled to room temperature over several hours. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 2000 mL of ethyl acetate. The particles are then dried overnight in a vacuum oven at ambient temperature. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 55 μm with a span of about 1.30.
[0287] Prophetic Example 8: REFLEX® Glitter Blue R-781E Pigment Reacted with 3-Aminopropyl (3-Oxobutanoic) Acid Functionalized Silica Nanoparticles and Crosslinked in Situ with Polyamide Resin To a 2 liter glass reactor equipped with an overhead mechanical stirrer and a heating mantle, 100 g of REFLEX® Glitter Blue pigment, product code R-781E (available from Creation of Quality Value Company Ltd.), suspended in 100 mL of 3-aminopropyl (3-oxobutanoic acid) acid functionalized silica nanoparticles (available from Millipore Sigma) as a colloidal dispersion at 2.5 wt % loading in 900 mL of deionized water and DMF, is added. The mixture is heated to 40° C. with vigorous stirring for 4 hours to promote the adsorption of the silica nanoparticles onto the surface of the pigment. The suspension is cooled to room temperature and filtered to remove the water and DMF solvent. The functionalized pigment particles with free carboxylic acid functional groups are dried in a vacuum oven at 40° C. for 24 hours to produce a functionalized pigment powder.
[0288] A clear, viscous stock solution (1.5 molar) of thionyl chloride (5.46 mL, 0.075 mol) and benzotriazole (8.93 g, 0.075 mol) in 50 mL of dry methylene chloride was prepared with mixing at room temperature. A portion of this solution (1.25 mmol) was added slowly to convert the pendant carboxylic acid functional groups on the surface of the mica pigment to acid chlorides, allowing curing by the aminopolyamide groups in the polyamide resin.
[0289] The dried mica pigment REFLEX® Glitter Blue functionalized with surface carboxylic acid (approximately 110 g) is suspended in 500 mL of dry methylene chloride with constant stirring. To this mixture, 20 mL of the thionyl chloride-benzotriazole mixture is slowly added over 30 minutes at room temperature. As the reaction proceeds, the benzotriazole hydrochloride salt begins to precipitate out of solution, indicating conversion of the carboxylic acid to the acid chloride. The reaction mixture is mixed for an additional 30 minutes, and then the mixture is filtered to remove the solvent and thoroughly washed with water before being dried in a vacuum oven for 24 hours.
[0290] Subsequently, 50 g of polyamide resin, such as nylon 6,6, is melt mixed with 10 g of the above acid chloride surface functionalized mica pigment, Reflex® Glitter Blue, in a Haake mixer at 150° C.-200° C. for 20-30 minutes to promote the crosslinking reaction of the acid chloride with the amino groups of the polyamide resin. The resulting pigment-pendant polyamide resin concentrate is discharged from the Haake mixer, cooled, and ground into a fine powder for subsequent incorporation into micrometer-sized particles of pigmented polyamide.
[0291] 1.5 g of Reflex® Glitter Blue pigment-pendant crosslinked polyamide resin on the pigment surface and 28.5 g of nylon 6,6 are melt mixed with 150 g of polydimethylsiloxane (PDMS) of specific viscosity 60,000 containing AEROSIL® R812S silica nanoparticles dispersed therein (0.75 wt.% with respect to PP-polyamide) by hot melt emulsification in a Haake mixer fitted with a 300 mL mixing vessel. The mixer is heated to 230° C. and mixed at 200 rpm for 20 minutes.
[0292] The mixture is then discharged from the Haake onto a cold surface resulting in rapid quench cooling. The resulting mixture is then filtered through a 90 mm WHATMAN® #1 filter paper (available from SigmaAldrich) to separate the PP-polyamide particles from the carrier fluid. The particles are washed three times with 1000 mL of ethyl acetate. The particles are then air-dried overnight in an aluminum pan in a fume hood. If desired, the dried particles can be sieved through a 150 μm sieve. The PP-polyamide particles are then characterized for size by a Malvern MASTERSIZER™ 3000 and for morphology by SEM micrographs. The D50 (μm) is predicted to be about 75 μm with a span of about 0.85.
[0293] Prophetic Example 9: General Epoxide and Polyamide Reaction Conditions The reaction of the epoxide groups on the metal pigment with the polyamide may be carried out under an atmosphere (nitrogen or argon) at a temperature of about 70°C to about 200°C (or about 70°C to about 150°C, about 125°C to about 200°C) in the presence of an organic solvent such as tetrahydrofuran, dimethylformamide, toluene, and any combination thereof. The mixture is then stirred at elevated temperature for about 24 hours. After the mixture is cooled to room temperature, the grafted polymer is filtered and washed to remove organic impurities and unreacted starting reagents.
[0294] Thus, the present invention is well adapted to attain the objects and advantages set forth above, as well as the advantages inherent therein. The specific embodiments and configurations disclosed above are merely illustrative, as the invention may be modified and practiced in different but equivalent manners apparent to those skilled in the art having the benefit of the teachings herein. Furthermore, no limitation is intended to the details of construction or design shown herein, other than as set forth in the following claims. Thus, it will be apparent that the specific exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are considered within the scope and spirit of the invention. The invention illustratively disclosed herein may be practiced in the absence of any element not specifically disclosed herein and / or any element disclosed herein. Although the compositions and methods are described in terms "comprising," "containing," or "including" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" various components and steps. All numbers and ranges disclosed above may vary somewhat. Whenever a numerical range with a lower and upper limit is disclosed, any number within that range and any included range is specifically disclosed. In particular, all ranges of values disclosed herein (in the form "from about a to about b," or equivalently "approximately a to b," or equivalently "from approximately a b") should be understood to describe all numbers and ranges encompassed within the broad range of values. Also, the terms in the claims have their plain and ordinary meaning unless expressly and unambiguously defined by the patentee. In addition, when used in the claims, the indefinite article "a" or "an" is defined herein to mean one or more than one of the elements it introduces. Yet another aspect of the present invention may be as follows. [1] A method comprising the steps of: functionalizing metal oxide particles attached to pigment particles with an epoxy-bearing compound to produce a surface treated pigment having a pendant epoxy; reacting the pendant epoxy with a polyamide to obtain a pigment-pendant polyamide (PP-polyamide). [2] The method according to [1] above, wherein the compound having the epoxide is selected from the group consisting of (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane, 1,3-bis(3-glycidyloxypropyl)tetramethylsiloxane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 5,6-epoxyhexyltriethoxysilane, and any combination thereof. [3] The method according to [1], wherein the metal oxide particles include one or more selected from the group consisting of titanium dioxide, titanium suboxide, titanium oxynitride, Al2O3, Fe2O3, Fe3O4, SnO2, Cr2O3, ZnO, CuO, NiO, zirconium oxide, and titanium iron oxide. [4] The method according to [1], wherein the pigment particles comprise one or more selected from the group consisting of synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO2 flakes, Al2O3 flakes, glass flakes, needle pigments, CaSO4, iron oxide, chromium oxide, carbon black, metal effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments. [5] The method according to [1], wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacine amide, polyundecane amide, polydodecanamide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, any copolymers thereof, and any combinations thereof. [6] The method according to [1], wherein the reacting of the pendant epoxy with the polyamide is carried out at about 70°C to about 200°C. [7] The method according to [1] above, wherein a weight ratio of the pigment to the polyamide is about 1:10 to about 1:1000. [8] A method comprising the steps of: functionalizing metal oxide particles attached to pigment particles with silica particles having a carboxylic acid surface treatment to produce a surface treated pigment having pendant carboxylic acid; converting said pendant carboxylic acid to a pendant acid chloride; reacting said pendant acid chloride with a polyamide to obtain a pigment-pendant polyamide (PP-polyamide). [9] The metal oxide particles are titanium dioxide, titanium suboxide, titanium oxynitride, Al 2 O 3 , Fe 2 O 3 , Fe 3 O 4 , SnO 2 、Cr 2 O 3 9. The method according to claim 8, further comprising at least one selected from the group consisting of ZnO, CuO, NiO, zirconium oxide, and titanium iron oxide.
[10] The pigment particles are synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO 2 Flake, Al 2 O 3 Flakes, glass flakes, needle pigments, CaSO 4 9. The method of claim 8, further comprising one or more selected from the group consisting of iron oxide, chromium oxide, carbon black, metal effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
[11] The method according to [8], wherein the silica particles having a carboxylic acid surface treatment include one or more selected from the group consisting of 3-aminopropyl-(3-oxobutanoic) acid functionalized silica, 3-propylsulfonic acid functionalized silica gel, propyl carboxylic acid functionalized silica, triaminetetraacetic acid functionalized silica gel, propionyl chloride functionalized silica gel, 3-carboxypropyl functionalized silica gel, aminomethylphosphonic acid (AMPA) functionalized silica gel, and 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) functionalized silica gel.
[12] The method according to [8], wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecanamide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, any copolymers thereof, and any combinations thereof.
[13] The method according to [8] above, wherein the reacting of the pendant acid chloride with the polyamide comprises melt mixing the pigment particles functionalized with the pendant acid chloride with the polyamide for 15 minutes to about 1 hour at about 125°C to about 250°C.
[14] The method according to [8], wherein the weight ratio of the pigment to the polyamide is about 1:10 to about 1:1000.
[15] A composition comprising: A composition comprising a polyamide having a pigment pendant from a backbone of the polyamide, the pigment comprising metal oxide particles on the surface of the pigment particles.
[16] The composition according to
[15] , wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacinamide, polyundecane amide, polydodecane amide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, any copolymers thereof, and any combinations thereof.
[17] The composition according to
[15] above, wherein a weight ratio of the pigment to the polyamide is about 1:10 to about 1:1000.
[18] The pigment particles are synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO 2 Flake, Al 2 O 3 Flakes, glass flakes, needle pigments, CaSO 4 , iron oxide, chromium oxide, carbon black, metal effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
[19] An article comprising the composition described in
[15] .
Claims
1. functionalizing metal oxide particles attached to pigment particles with an epoxy-bearing compound to produce a surface treated pigment having a pendant epoxy; reacting the pendant epoxy with nitrogen elements of the polyamide backbone to obtain a pigment-pendant polyamide (PP-polyamide); wherein said metal oxide particles are different particles from said pigment particles.
2. 2. The method of claim 1, wherein the compound having the epoxide is selected from the group consisting of (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane, and 1,3-bis(3-glycidyloxypropyl)tetramethylsiloxane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 5,6-epoxyhexyltriethoxysilane, and any combination thereof.
3. The metal oxide particles include titanium dioxide, titanium suboxide, titanium oxynitride, Al 2 O 3 , Fe 2 O 3 , Fe 3 O 4 , SnO 2 , Cr 2 O 3 , ZnO, CuO, NiO, zirconium oxide, and iron titanium oxide.
4. The pigment particles include synthetic mica, natural mica, talc, sericite, kaolin, glass, SiO 2 Flakes, Al 2 O 3 Flakes, glass flakes, needle pigments, CaSO 4 , iron oxide, chromium oxide, carbon black, metallic effect pigments, optically variable pigments, liquid crystal polymer pigments, and holographic pigments.
5. 2. The method of claim 1, wherein the polyamide is selected from the group consisting of polycaproamide, poly(hexamethylene succinamide), polyhexamethylene adipamide, polypentamethylene adipamide, polyhexamethylene sebacamide, polyundecane amide, polydodecane amide, polyhexamethylene terephthalamide, nylon 10,10, nylon 10,12, nylon 10,14, nylon 10,18, nylon 6,18, nylon 6,12, nylon 6,14, nylon 12,12, semi-aromatic polyamides, aromatic polyamides, copolymers of any of these, and any combination thereof.
6. 10. The method of claim 1, wherein the reacting of the pendant epoxy with nitrogen elements of the polyamide backbone is carried out at 70°C to 200°C.
7. The method of claim 1, wherein the weight ratio of said pigment to said polyamide is from 1:10 to 1:1000.
Citation Information
Patent Citations
Dispersion composition of aluminum pigment, and manufacturing method thereof
JP2015078321A
Coated metallic pigments, methods for making and using same, coatings, and articles
JP2017508016A
Plate-like PVD aluminum pigment with a protective encapsulation and method for manufacturing a plate-like PVD aluminium pigment with a protective encapsulation
WO2019110490A1